Secondary battery and electric device

CN116964770BActive Publication Date: 2026-10-09CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380010375.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2026-10-09
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

然而,目前面临的问题是:在提高二次电池的能量密度时,往往延长二次电池的充电时间

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116964770B_ABST
    Figure CN116964770B_ABST
Patent Text Reader

Abstract

The application provides a secondary battery and a power consumption device, the secondary battery comprising a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode film layer, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, a thickness of the negative electrode film layer is recorded as H, a region within a thickness range of 0.3H from the second surface of the negative electrode film layer is recorded as a first region of the negative electrode film layer, a region within a thickness range of 0.3H from the first surface of the negative electrode film layer is recorded as a second region of the negative electrode film layer, the first region comprises a first active material, the second region comprises a second active material, the first active material comprises a first silicon-based material, and the first silicon-based material comprises secondary particles aggregated by primary particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to a secondary battery and an electrical device. Background Technology

[0002] In recent years, rechargeable batteries have been widely used in energy storage systems for hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other fields. With the increasingly widespread application of rechargeable batteries, significant challenges have been placed on their performance, such as the requirement for high energy density and short charging times. However, the current problem is that increasing the energy density of rechargeable batteries often leads to a longer charging time. Summary of the Invention

[0003] This application provides a secondary battery and an electrical device that enables the secondary battery to achieve both high energy density and good fast charging performance.

[0004] The first aspect of this application provides a secondary battery, including a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer, the negative electrode film layer having a first surface away from the negative current collector and a second surface disposed opposite to the first surface, the thickness of the negative electrode film layer is denoted as H, the region from the second surface of the negative electrode film layer to a thickness range of 0.3H is denoted as the first region of the negative electrode film layer, and the region from the first surface of the negative electrode film layer to a thickness range of 0.3H is denoted as the second region of the negative electrode film layer.

[0005] The first region includes a first active material, the second region includes a second active material, the first active material includes a first silicon-based material, and the first silicon-based material includes secondary particles formed by the aggregation of primary particles.

[0006] In the negative electrode sheet of this application, the first active material in the first region of the negative electrode film layer includes a silicon-based material with secondary particles. This improves the pore structure of the first region of the negative electrode film layer, enhances the wetting and retention characteristics of the negative electrode film layer with electrolyte, and allows ions to be rapidly transported to the surface of the first active material particles. Furthermore, the silicon-based material with secondary particles provides more ion insertion channels, which also facilitates the rapid diffusion of ions from the particle surface to the bulk phase. Therefore, the negative electrode sheet of this application is beneficial for improving the fast-charging performance of high-energy-density secondary batteries and for achieving ultra-fast charging goals. In addition, the first active material includes a silicon-based material with secondary particles. The silicon-based material with secondary particles has poor compressive strength. By improving the structure of the negative electrode film layer, the damage to the particle structure of the silicon-based material caused by rolling pressure can be reduced, thereby fully utilizing the high capacity advantage of the first silicon-based material. Therefore, the negative electrode sheet of this application enables secondary batteries to achieve both high energy density and good fast-charging performance.

[0007] In any embodiment of this application, the proportion of the first silicon-based material in the secondary particles is ≥55%, and can be selected as 60%-85%. This is beneficial for the secondary battery to achieve both good fast-charging performance and cycle performance.

[0008] In any embodiment of this application, the first active material includes a first carbon-based material, which can improve the electronic conductivity of the negative electrode film, thereby improving the fast charging performance and energy density of the secondary battery while ensuring good cycle performance.

[0009] In any embodiment of this application, the surface of the first carbon-based material does not have a carbon coating layer.

[0010] In any embodiment of this application, the first carbon-based material comprises secondary particles formed by the aggregation of primary particles.

[0011] In any embodiment of this application, the proportion of the first carbon-based material in the secondary particles is ≥65%, and can be selected as 70%-95%. This is beneficial for the secondary battery to achieve both good fast-charging performance and cycle performance.

[0012] In any embodiment of this application, the volumetric particle size Dv50 of the first carbon-based material is 12-18 μm, optionally 14-16 μm. When the volumetric particle size Dv50 of the first carbon-based material is within the above range, it is beneficial to improve the transport performance of ions and electrons, thereby further improving the fast-charging performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the first carbon-based material, reduce side reactions, and thus further improve the cycle performance of the secondary battery.

[0013] In any embodiment of this application, the volume distribution particle size Dv90 of the first carbon-based material is 24-30 μm, optionally 25-29 μm. When the volume distribution particle size Dv90 of the first carbon-based material is within the above range, the uniformity of the first carbon-based material particles is better, which is beneficial to improving the ion and electron transport performance, thereby further improving the fast charging performance of the secondary battery.

[0014] In any embodiment of this application, the first carbon-based material satisfies (Dv90-Dv10) / Dv50 of 0.8-1.6, optionally 1.0-1.3. When (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, it is beneficial for the first region of the negative electrode film to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transport and further improving the fast charging performance of the secondary battery; in addition, the first carbon-based material also has good particle packing performance, which is beneficial to increasing the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0015] In any embodiment of this application, the specific surface area of ​​the first carbon-based material is 2.0-4.0 m². 2 / g, can be selected as 2.5-3.1m 2 / g. When the specific surface area of ​​the first carbon-based material is within the above-mentioned range, it can increase the ion insertion channels in the first region of the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the first carbon-based material is within the above-mentioned range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have good cycle performance.

[0016] In any embodiment of this application, the powder compaction density of the first carbon-based material at 20000N is 1.8-2.0 g / cm³. 3 The selectable value is 1.85-1.95 g / cm³. 3 When the compaction density of the first carbon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0017] In any embodiment of this application, the tap density of the first carbon-based material is 0.9-1.1 g / cm³. 3 The selectable value is 0.95-1.05 g / cm³. 3When the tap density of the first carbon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0018] In any embodiment of this application, the graphitization degree of the first carbon-based material is ≥93%, and can be selected as 93%-95%. When the graphitization degree of the first carbon-based material is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film, thereby enabling the secondary battery to achieve both high energy density and good fast charging performance.

[0019] In any embodiment of this application, the specific capacity of the first carbon-based material is ≥355mAh / g, optionally 357-364mAh / g. When the specific capacity of the first carbon-based material is within the above range, it can improve the energy density of the secondary battery and also give the first carbon-based material good ion transport performance, thereby also helping to improve the fast charging performance of the secondary battery.

[0020] In any embodiment of this application, the powder OI value of the first carbon-based material is 3-10, optionally 5-8. The lower powder OI value of the first carbon-based material allows it to quickly receive ions from the positive electrode, thereby further improving the fast-charging performance of the secondary battery.

[0021] In any embodiment of this application, the volumetric particle size Dv50 of the first carbon-based material is denoted as A, in μm, and the specific surface area of ​​the first carbon-based material is denoted as B, in m³. 2 If the ratio is 4-11, then A / B can be selected as 5-7. Adjusting A / B within this range increases the ion insertion channels in the negative electrode film, facilitating rapid diffusion of ions from the particle surface to the bulk phase, thus further optimizing the fast-charging performance of the secondary battery. Furthermore, it helps reduce side reactions, thereby enabling the secondary battery to have good cycle performance.

[0022] In any embodiment of this application, the first carbon-based material includes graphite, and optionally, the graphite includes artificial graphite.

[0023] In any embodiment of this application, the mass percentage of the first carbon-based material in the first active material is ≥50%, and can be selected as 60%-98%. By adjusting the content of the first carbon-based material within the above range, the electronic conductivity of the negative electrode film can be improved, thereby improving the fast charging performance of the secondary battery while ensuring good cycle performance.

[0024] In any embodiment of this application, the first active material includes a first carbon-based material, the second active material includes a second carbon-based material, the first carbon-based material includes secondary particles formed by the aggregation of primary particles, and the second carbon-based material includes secondary particles formed by the aggregation of primary particles.

[0025] In any embodiment of this application, the proportion of the second carbon-based material in the secondary particles is less than the proportion of the first carbon-based material in the first carbon-based material. By adjusting the proportion of the second carbon-based material in the secondary particles to be less than the proportion of the first carbon-based material in the first carbon-based material, it is beneficial to reduce side reactions and improve the cycle performance of the secondary battery.

[0026] In any embodiment of this application, the volume distribution particle size Dv50 of the second carbon-based material is smaller than that of the first carbon-based material. By making the volume distribution particle size Dv50 of the second carbon-based material smaller than that of the first carbon-based material, the second region and the first region of the negative electrode film can have a good compaction density difference. As a result, the pore distribution and ion concentration distribution in the thickness direction of the negative electrode film are better matched, which is beneficial to improving the wetting and retention characteristics of the negative electrode film with the electrolyte and to ion transport. This enables the secondary battery to achieve both good fast charging performance and cycle performance.

[0027] In any embodiment of this application, the specific surface area of ​​the second carbon-based material is smaller than that of the first carbon-based material. By making the specific surface area of ​​the second carbon-based material smaller than that of the first carbon-based material, it is beneficial to reduce side reactions, thereby enabling the secondary battery to achieve both good fast-charging performance and cycle performance.

[0028] In any embodiment of this application, the powder compaction density of the second carbon-based material at 20000N is less than that of the first carbon-based material at 20000N. By making the powder compaction density of the second carbon-based material at 20000N less than that of the first carbon-based material at 20000N, the second and first regions of the negative electrode film can have good pore distribution and better match the concentration distribution of ions in the thickness direction of the negative electrode film, reducing the difficulty of ion liquid phase transport and improving the wetting and retention characteristics of the negative electrode film to the electrolyte. This enables the secondary battery to achieve both good fast charging performance and cycle performance.

[0029] In any embodiment of this application, the tap density of the second carbon-based material is greater than that of the first carbon-based material. By making the tap density of the second carbon-based material greater than that of the first carbon-based material, the second region of the negative electrode film can achieve both good fast-charging performance and high energy density.

[0030] In any embodiment of this application, the degree of graphitization of the second carbon-based material is less than that of the first carbon-based material. By adjusting the degree of graphitization of the second carbon-based material to be less than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good fast-charging performance.

[0031] In any embodiment of this application, the specific capacity of the second carbon-based material is less than that of the first carbon-based material. By adjusting the specific capacity of the second carbon-based material to be less than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good fast-charging performance.

[0032] In any embodiment of this application, the OI value of the second carbon-based material powder is lower than that of the first carbon-based material powder. By adjusting the OI value of the second carbon-based material powder to be lower than that of the first carbon-based material powder, it is beneficial to the rapid insertion and extraction of ions, thereby enabling the secondary battery to have better fast-charging performance.

[0033] In any embodiment of this application, the second carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the second carbon-based material in the secondary particles is ≥60%, optionally 65%-90%. This is beneficial for the secondary battery to better combine good fast-charging performance and cycle performance.

[0034] In any embodiment of this application, the surface of the second carbon-based material has a carbon coating layer, optionally comprising hard carbon. The presence of the carbon coating layer can increase ion diffusion channels, thereby facilitating further optimization of the fast-charging performance of the secondary battery.

[0035] In any embodiment of this application, the volume distribution particle size Dv50 of the second carbon-based material is 10-17 μm, and can be selected as 13-15 μm.

[0036] In any embodiment of this application, the volume distribution particle size Dv90 of the second carbon-based material is 18-26 μm, and can be optionally 21-25 μm.

[0037] When the volume distribution particle sizes Dv50 and Dv90 of the second carbon-based material are within the above range, it is beneficial to improve the transport performance of ions and electrons, thereby further improving the fast charging performance of the secondary battery.

[0038] In any embodiment of this application, the second carbon-based material satisfies (Dv90-Dv10) / Dv50 of 0.6-1.4, optionally 0.8-1.2. When (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, it is beneficial for the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, thereby further improving the fast charging performance of the secondary battery; in addition, the second carbon-based material also has good particle packing performance, which is beneficial to increasing the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0039] In any embodiment of this application, the specific surface area of ​​the second carbon-based material is 1.5-3.0 m². 2 / g, can be selected as 1.8-2.5m 2 / g. When the specific surface area of ​​the second carbon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the second carbon-based material is within the above range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0040] In any embodiment of this application, the powder compaction density of the second carbon-based material at 20000N is 1.65-1.85 g / cm³. 3 The selectable value is 1.70-1.80 g / cm³. 3 When the compaction density of the second carbon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0041] In any embodiment of this application, the tap density of the second carbon-based material is 1.0-1.2 g / cm³. 3 The selectable value is 1.05-1.15 g / cm³. 3 When the tap density of the second carbon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0042] In any embodiment of this application, the graphitization degree of the second carbon-based material is ≥91%, optionally 92%-94%. When the graphitization degree of the second carbon-based material is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film, thereby enabling the secondary battery to achieve both high energy density and good fast charging performance.

[0043] In any embodiment of this application, the specific capacity of the second carbon-based material is ≥352 mAh / g, optionally 355-359 mAh / g. When the specific capacity of the second carbon-based material is within the above range, it can improve the energy density of the secondary battery and also enable the carbon-based material to have good ion transport performance, thereby also improving the fast charging performance of the secondary battery.

[0044] In any embodiment of this application, the OI value of the second carbon-based material powder is 2-8, optionally 3-6. The lower OI value of the second carbon-based material powder allows it to quickly receive ions from the positive electrode, thereby further improving the fast-charging performance of the secondary battery.

[0045] In any embodiment of this application, the volumetric particle size Dv50 of the second carbon-based material is denoted as C, with units of μm, and the specific surface area of ​​the second carbon-based material is denoted as D, with units of m². 2 If the C / D ratio is within the specified range (g), then the C / D ratio is 3-9, and can be selected as 4-6. Adjusting the C / D ratio within this range increases the ion insertion channels in the negative electrode film, facilitating the rapid diffusion of ions from the surface of the second carbon-based material particles to the bulk phase, thus further optimizing the fast-charging performance of the secondary battery. Furthermore, it helps reduce side reactions, thereby improving the cycle performance of the secondary battery.

[0046] In any embodiment of this application, the second carbon-based material includes graphite, and optionally, the graphite includes artificial graphite.

[0047] In any embodiment of this application, the mass percentage of the second carbon-based material in the second active material is ≥70%, optionally 75%-95%. This is beneficial for improving the fast-charging performance of the secondary battery.

[0048] In any embodiment of this application, the porosity of the first silicon-based material of the secondary particles is ≥4%, optionally 5%-20%. Further adjusting the porosity of the first silicon-based material of the secondary particles is beneficial for further optimization of the fast-charging performance of the secondary battery.

[0049] In any embodiment of this application, the volume distribution particle size Dv50 of the first silicon-based material is 8-15 μm, and can be selected as 10-13 μm.

[0050] In any embodiment of this application, the volume distribution particle size Dv90 of the first silicon-based material is 15-25 μm, and can be optionally 16-24 μm.

[0051] When the volume distribution particle size Dv50 and / or Dv90 of the first silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film layer, which is conducive to the rapid diffusion of ions from the particle surface to the bulk phase, thereby facilitating further optimization of the fast charging performance of the secondary battery.

[0052] In any embodiment of this application, the first silicon-based material satisfies (Dv90-Dv10) / Dv50 of 0.7-1.5, optionally 0.9-1.3. When (Dv90-Dv10) / Dv50 of the first silicon-based material is within the above range, it is beneficial for the first region of the negative electrode film to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transport and improving the fast charging performance of the secondary battery; in addition, the first silicon-based material can also have good particle packing performance, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0053] In any embodiment of this application, the specific surface area of ​​the first silicon-based material is 0.7-2.0 m². 2 / g, selectable from 0.8-1.6m 2 / g. When the specific surface area of ​​the first silicon-based material is within the above-mentioned range, it can increase the ion insertion channels in the negative electrode film layer, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the first silicon-based material is within the above-mentioned range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0054] In any embodiment of this application, the powder compaction density of the first silicon-based material at 50000N is 1.0-1.7 g / cm³. 3 The concentration can be selected as 1.2-1.6 g / cm³. 3 When the compaction density of the first silicon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0055] In any embodiment of this application, the tap density of the first silicon-based material is 1.0-1.5 g / cm³. 3 The concentration can be selected as 1.1-1.4 g / cm³. 3When the tap density of the first silicon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0056] In any embodiment of this application, the powder resistivity of the first silicon-based material at 4 MPa is ≤15 Ω·cm, and can be selected as 0.5-12 Ω·cm. By adjusting the powder resistivity of the first silicon-based material within the above range, the electronic conductivity of the negative electrode film can be improved, and the fast-charging performance of the secondary battery can be further improved.

[0057] In any embodiment of this application, the mass percentage of the first silicon-based material in the first active material is ≤50%, and can be selected as 2%-40%. By adjusting the content of the first silicon-based material within the above range, the fast-charging performance and energy density of the secondary battery can be improved while ensuring good cycle performance.

[0058] In any embodiment of this application, the first silicon-based material includes one or more of elemental silicon, silicon oxide, silicon carbon material, and silicon alloy material. Optionally, the first silicon-based material includes secondary particles aggregated from at least one of the following primary particles: primary particles of silicon-oxygen material that does not contain alkali metals and alkaline earth metals, primary particles of silicon-oxygen material that contains alkali metals or alkaline earth metals, primary particles of silicon carbon material, primary particles of elemental silicon, and primary particles of silicon alloy.

[0059] In any embodiment of this application, the second active material includes a second silicon-based material, thereby further improving the energy density of the secondary battery.

[0060] In any embodiment of this application, the second silicon-based material includes one or more of primary particles and secondary particles formed by the aggregation of primary particles, and optionally includes primary particles.

[0061] In any embodiment of this application, the second silicon-based material comprises primary particles, and the proportion of the primary particles in the second silicon-based material is ≥60%, optionally 65%-95%. When the second silicon-based material is mainly composed of primary particles, it is beneficial to reduce the probability of particle breakage, increase the compaction density of the negative electrode film, and thus further improve the energy density of the secondary battery.

[0062] In any embodiment of this application, the mass percentage of the second silicon-based material in the second active material is less than the mass percentage of the first silicon-based material in the first active material. By making the mass percentage of the second silicon-based material in the second active material less than the mass percentage of the first silicon-based material in the first active material, side reactions can be reduced, thereby contributing to better cycle performance of the secondary battery.

[0063] In any embodiment of this application, the volume distribution particle size Dv50 of the second silicon-based material is smaller than that of the first silicon-based material. By adjusting the volume distribution particle size Dv50 of the second silicon-based material to be smaller than that of the first silicon-based material, the probability of particle breakage of the second silicon-based material can be reduced, the electronic conductivity of the second silicon-based material can be increased, and the ion insertion channels of the negative electrode film can be increased. This enables the secondary battery to achieve both high energy density and good fast charging performance.

[0064] In any embodiment of this application, the specific surface area of ​​the second silicon-based material is smaller than that of the first silicon-based material. When the specific surface area of ​​the second silicon-based material is smaller than that of the first silicon-based material, it is beneficial to reduce side reactions, thereby contributing to better cycle performance of the secondary battery.

[0065] In any embodiment of this application, the powder compaction density of the second silicon-based material at 50,000 N is greater than that of the first silicon-based material at 50,000 N. By adjusting the powder compaction density of the second silicon-based material to be greater than that of the first silicon-based material, it is beneficial to improve the energy density of the secondary battery and enhance its cycle performance.

[0066] In any embodiment of this application, the tap density of the second silicon-based material is greater than that of the first silicon-based material. By adjusting the tap density of the second silicon-based material to be greater than that of the first silicon-based material, it is beneficial to improve the energy density and cycle performance of the secondary battery.

[0067] In any embodiment of this application, the powder resistivity of the second silicon-based material at 4 MPa is less than that of the first silicon-based material at 4 MPa. By adjusting the powder resistivity of the second silicon-based material to be less than that of the first silicon-based material, it is beneficial to improve the electronic conductivity of the negative electrode film, thereby further improving the fast-charging performance of the secondary battery.

[0068] In any embodiment of this application, the volume distribution particle size Dv50 of the second silicon-based material is 4-12 μm, and can be selected as 5-11 μm.

[0069] In any embodiment of this application, the volume distribution particle size Dv90 of the second silicon-based material is 8-18 μm, and can be selected as 9-17 μm.

[0070] When the volume distribution particle size Dv50 and / or Dv90 of the second silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film layer, which is conducive to the rapid diffusion of ions from the particle surface to the bulk phase, thereby facilitating further optimization of the fast charging performance of the secondary battery; at the same time, it can also reduce the risk of particle breakage of the second silicon-based material.

[0071] In any embodiment of this application, the second silicon-based material satisfies (Dv90-Dv10) / Dv50 of 0.7-1.3, optionally 0.8-1.2. When (Dv90-Dv10) / Dv50 of the second silicon-based material is within the above range, it is beneficial for the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, thereby further improving the fast charging performance of the secondary battery; in addition, the second silicon-based material can also have good particle packing performance, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0072] In any embodiment of this application, the specific surface area of ​​the second silicon-based material is 0.6-1.6 m². 2 / g, selectable from 0.7-1.5m 2 / g. When the specific surface area of ​​the second silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the second silicon-based material is within the above range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0073] In any embodiment of this application, the powder compaction density of the second silicon-based material at 50000N is 1.2-1.8 g / cm³. 3 The concentration can be selected as 1.3-1.7 g / cm³. 3 When the compaction density of the second silicon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0074] In any embodiment of this application, the tap density of the second silicon-based material is 1.1-1.7 g / cm³. 3 The concentration can be selected as 1.2-1.6 g / cm³. 3When the tap density of the second silicon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, which can further reduce the difficulty of ion liquid phase transport, improve ion and electron transport performance, and improve the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0075] In any embodiment of this application, the powder resistivity of the second silicon-based material at 4 MPa is ≤5 Ω·cm, and can be selected as 0.3-4 Ω·cm. By adjusting the powder resistivity of the second silicon-based material within the above range, the electronic conductivity of the negative electrode film can be improved, and the fast-charging performance of the secondary battery can be further improved.

[0076] In any embodiment of this application, the mass percentage of the second silicon-based material in the second active material is ≤30%, and optionally ≤15%. By adjusting the content of the second silicon-based material within the above range, the fast-charging performance and energy density of the secondary battery can be improved while ensuring good cycle performance.

[0077] In any embodiment of this application, the second silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, and silicon alloy materials.

[0078] In any embodiment of this application, the intermediate region located between the first region and the second region includes the first active material and / or the second active material.

[0079] In any embodiment of this application, the porosity of the negative electrode film is ≥18%, and can be selected as 25%-45%. This is beneficial for the negative electrode film to achieve both high capacity and suitable pore structure, which in turn is beneficial for the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0080] In any embodiment of this application, the compaction density of the negative electrode film layer is ≥1.5 g / cm³. 3 The selectable value is 1.6-1.8 g / cm³. 3 This allows the negative electrode film to achieve both high capacity and good ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0081] In any embodiment of this application, the areal density of the negative electrode film is ≥7 mg / cm³. 2 12-30 mg / cm³ is an option. 2This allows the negative electrode film to achieve both high capacity and good ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0082] A second aspect of this application provides an electrical device that includes the secondary battery of the first aspect of this application.

[0083] The electrical device of this application includes the secondary battery provided in this application, and therefore has at least the same advantages as the secondary battery. Attached Figure Description

[0084] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0085] Figure 1 This is a schematic diagram of one embodiment of the negative electrode sheet of this application.

[0086] Figure 2 This is a schematic diagram of another embodiment of the negative electrode sheet of this application.

[0087] Figure 3 This is a schematic diagram of another embodiment of the negative electrode sheet of this application.

[0088] Figure 4 This is a schematic diagram of one embodiment of the secondary battery of this application.

[0089] Figure 5 This is an exploded view of one embodiment of the secondary battery of this application.

[0090] Figure 6 This is a schematic diagram of one embodiment of the battery module of this application.

[0091] Figure 7 This is a schematic diagram of one embodiment of the battery pack of this application.

[0092] Figure 8 yes Figure 7 An exploded view of an embodiment of the battery pack shown.

[0093] Figure 9 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application.

[0094] In the accompanying drawings, the figures may not be drawn to scale. The reference numerals are explained as follows: 1 Battery pack, 2 Upper casing, 3 Lower casing, 4 Battery module, 5 Secondary battery, 51 Housing, 52 Electrode assembly, 53 Cover plate, 10 Negative electrode sheet, 101 Negative current collector, 102 Negative electrode film, 102a First surface, 102b Second surface, 1021 First region, 1022 Second region, 1023 Intermediate region. Detailed Implementation

[0095] The embodiments of the secondary battery and power-consuming device of this application are hereby disclosed in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0096] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0097] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0098] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0099] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0100] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0101] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0102] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0103] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, such as the testing methods provided in this application. Unless otherwise specified, the testing temperature is 25°C.

[0104] In this application, the terms "multiple" or "various" refer to two or more kinds of things.

[0105] Energy density and fast-charging performance are two key performance indicators for rechargeable batteries, but these two properties are often contradictory. High-energy-density batteries typically require high electrode compaction density, high film thickness, and low porosity, which usually hinders ion transport and thus adversely affects the fast-charging performance of the rechargeable battery. Good fast-charging performance usually requires sacrificing energy density, for example, by requiring low electrode compaction density, low film thickness, and high porosity.

[0106] Therefore, how to make high-energy-density batteries also have good fast-charging performance is a technical problem that urgently needs to be solved.

[0107] As a crucial component of rechargeable batteries, the performance of the negative electrode significantly impacts the overall battery performance. Currently, graphite is the most commonly used negative electrode active material, but the energy density of rechargeable batteries using it is already close to the theoretical value. Silicon-based materials offer the advantage of high theoretical energy density, which can significantly improve the energy density of rechargeable batteries; however, the fast-charging performance of these batteries remains poor and requires further improvement.

[0108] In view of this, the inventors ingeniously improved the composition of the negative electrode film, which enables the secondary battery to achieve both high energy density and good fast charging performance.

[0109] Specifically, this application provides a secondary battery.

[0110] This application does not impose any particular limitation on the type of secondary battery; for example, the secondary battery can be a lithium-ion battery. Typically, a secondary battery includes a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the secondary battery, ions move back and forth between the positive and negative electrodes, inserting and extracting, with the electrolyte acting as a conductor for these ions. This application does not impose any particular limitation on the type of electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solutions). Secondary batteries using electrolyte solutions, and some secondary batteries using solid electrolytes, may also include a separator membrane, which is disposed between the positive and negative electrodes and primarily serves a separating function.

[0111] [Negative electrode plate]

[0112] Figures 1 to 3 This is a schematic diagram illustrating an embodiment of the negative electrode sheet of this application.

[0113] like Figures 1 to 3 As shown, the negative electrode 10 includes a negative current collector 101 and a negative electrode film 102 formed on at least one surface of the negative current collector 101. The negative electrode film 102 has a first surface 102a away from the negative current collector 101 and a second surface 102b disposed opposite to the first surface 102a. The thickness of the negative electrode film 102 is denoted as H. The region from the second surface 102b of the negative electrode film to a thickness range of 0.3H is denoted as the first region 1021 of the negative electrode film, and the region from the first surface 102a of the negative electrode film to a thickness range of 0.3H is denoted as the second region 1022 of the negative electrode film.

[0114] The first region 1021 includes a first active material, and the second region 1022 includes a second active material. The first active material includes a first silicon-based material, which includes secondary particles formed by the aggregation of primary particles.

[0115] The thickness H of the negative electrode film refers to the thickness of the negative electrode film located on one side of the negative electrode current collector.

[0116] In high-energy-density battery systems, ion transport in the liquid phase has become a bottleneck restricting the fast-charging performance of rechargeable batteries. Taking a high-energy-density negative electrode as an example, the porosity of the second region of the negative electrode film is usually larger, while the porosity of the first region of the negative electrode film is usually smaller. This results in greater resistance to ion transport in the liquid phase in the first region of the negative electrode film and more difficult electrolyte wetting, which in turn affects the kinetic performance of the negative electrode and the rechargeable battery, making it difficult for the rechargeable battery to achieve the goal of ultra-fast charging.

[0117] In the negative electrode sheet of this application, the first active material in the first region of the negative electrode film layer includes a silicon-based material of secondary particles. This material improves the pore structure of the first region of the negative electrode film layer, enhances the wetting and retention characteristics of the negative electrode film layer with electrolyte, and allows ions to be rapidly transported to the surface of the first active material particles. Furthermore, the silicon-based material of secondary particles can provide more ion insertion channels, which also facilitates the rapid diffusion of ions from the particle surface to the bulk phase. Therefore, the negative electrode sheet of this application is beneficial for improving the fast-charging performance of high-energy-density secondary batteries and for achieving ultra-fast charging goals.

[0118] In addition, the first active material includes secondary silicon-based material. The secondary silicon-based material has poor compressive strength. By improving the structure of the negative electrode film, the damage to the particle structure of the secondary silicon-based material caused by the rolling pressure can be reduced, thereby giving full play to the high capacity advantage of the first silicon-based material.

[0119] Therefore, the negative electrode sheet of this application can enable the secondary battery to achieve both high energy density and good fast charging performance.

[0120] In some embodiments, the proportion of the first silicon-based material in the secondary particles can be ≥55%, such as ≥57.5%, ≥60%, ≥62.5%, ≥65%, etc. In high-energy-density battery systems, the porosity of the first region of the negative electrode film is often low, making ion liquid-phase transport difficult. By including an appropriate proportion of secondary particles in the first silicon-based material, the pore structure of the first region of the negative electrode film can be improved, thereby reducing the difficulty of ion liquid-phase transport and improving the fast-charging performance of the secondary battery; in addition, it is also beneficial for ions to be rapidly transported to the surface of the first silicon-based material particles, further optimizing the fast-charging performance of the secondary battery.

[0121] Further research by the inventors revealed that the proportion of the first silicon-based material in the secondary particles should not be too high, as this would lead to more side reactions in the secondary battery, affecting its cycle performance. Optionally, in some embodiments, the proportion of the first silicon-based material in the secondary particles can be 55%-90%, 60%-90%, 65%-90%, 55%-85%, 60%-85%, 65%-85%, 55%-80%, 60%-80%, or 65%-80%. This allows the secondary battery to achieve both good fast-charging and cycle performance.

[0122] In some embodiments, the first silicon-based material may further include primary particles (referring to non-agglomerated particles), and the proportion of the primary particles in the first silicon-based material may be ≤45%. The specific types of the primary particles and the secondary particles may be the same or different.

[0123] In some embodiments, the porosity of the first silicon-based material of the secondary particles can be ≥4%, optionally 5%-20%. The inventors further noted that by further adjusting the porosity of the first silicon-based material of the secondary particles, it is beneficial to further optimize the fast-charging performance of the secondary battery. When the porosity of the first silicon-based material of the secondary particles is within the above-mentioned range, it is beneficial to improve the pore structure of the first region of the negative electrode film, enhance the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby accelerating the ion liquid phase transport rate; it also helps to increase the ion intercalation channels of the first silicon-based material, allowing ions to diffuse rapidly from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery.

[0124] In some embodiments, the volume distribution particle size Dv50 of the first silicon-based material can be 8-15 μm, and optionally 10-13 μm.

[0125] In some embodiments, the volume distribution particle size Dv90 of the first silicon-based material can be 15-25 μm, and optionally 16-24 μm.

[0126] When the volume distribution particle size Dv50 and / or Dv90 of the first silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film layer, which is conducive to the rapid diffusion of ions from the particle surface to the bulk phase, thereby facilitating further optimization of the fast charging performance of the secondary battery.

[0127] In some embodiments, the first silicon-based material satisfies that (Dv90-Dv10) / Dv50 can be 0.7-1.5, and optionally 0.9-1.3. When (Dv90-Dv10) / Dv50 of the first silicon-based material is within the above range, it is beneficial for the first region of the negative electrode film to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transport and improving the fast charging performance of the secondary battery; in addition, the first silicon-based material can also have good particle packing performance, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0128] In some embodiments, the specific surface area of ​​the first silicon-based material may be 0.7-2.0 m². 2 / g, selectable from 0.8-1.6m 2 / g. When the specific surface area of ​​the first silicon-based material is within the above-mentioned range, it can increase the ion insertion channels in the negative electrode film layer, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the first silicon-based material is within the above-mentioned range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0129] In some embodiments, the powder compaction density of the first silicon-based material at 50000N can be 1.0-1.7 g / cm³. 3 The concentration can be selected as 1.2-1.6 g / cm³. 3 When the compaction density of the first silicon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0130] In some embodiments, the tap density of the first silicon-based material may be 1.0-1.5 g / cm³. 3 The concentration can be selected as 1.1-1.4 g / cm³. 3 When the tap density of the first silicon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0131] In some embodiments, the powder resistivity of the first silicon-based material at 4 MPa may be ≤15 Ω·cm, and may alternatively be 0.5-12 Ω·cm. When the powder resistivity of the first silicon-based material is adjusted within the above range, the electronic conductivity of the negative electrode film can be improved, and the fast charging performance of the secondary battery can be further enhanced.

[0132] In some embodiments, the mass percentage of the first silicon-based material in the first active material may be ≤50%, and may alternatively be 2%-40%, 2%-30%, 2%-20%, 2%-15%, 3%-40%, 3%-30%, 3%-20%, 3%-15%. When the content of the first silicon-based material is adjusted within the above range, the fast charging performance and energy density of the secondary battery can be improved, while enabling the secondary battery to have both good cycling performance.

[0133] In some embodiments, the first silicon-based material may include elemental silicon, silicon oxide (SiO x , 0 < x ≤ 2), one or more of silicon-carbon materials and silicon alloy materials. The present application does not impose specific limitations on the structure of the silicon-carbon material. For example, high-energy ball milling may be used to disperse nano-silicon in a carbon material, disperse nano-silicon in porous carbon, disperse a carbon material in porous silicon, coat a carbon material on the surface of nano-silicon, or co-deposit nano-silicon and nano-carbon together, etc.

[0134] In some embodiments, the first silicon-based material may include secondary particles formed by aggregating at least one of the following primary particles: primary particles of silicon-oxygen material containing no alkali metal and no alkaline earth metal, primary particles of silicon-oxygen material containing alkali metal or alkaline earth metal, primary particles of silicon-carbon material, primary particles of elemental silicon, and primary particles of silicon alloy. Optionally, the alkali metal may include Li. Optionally, the alkaline earth metal may include Mg. For example, the first silicon-based material may include secondary particles formed by aggregating primary particles of silicon-oxygen material containing no alkali metal and no alkaline earth metal, secondary particles formed by aggregating primary particles of silicon-oxygen material containing no alkali metal and no alkaline earth metal and primary particles of silicon-oxygen material containing alkali metal or alkaline earth metal, secondary particles formed by aggregating primary particles of silicon-oxygen material containing alkali metal or alkaline earth metal, secondary particles formed by aggregating primary particles of silicon-carbon material, secondary particles formed by aggregating primary particles of silicon-carbon material and primary particles of silicon-oxygen material containing no alkali metal and no alkaline earth metal, and secondary particles formed by aggregating primary particles of silicon-carbon material and primary particles of silicon-oxygen material containing alkali metal or alkaline earth metal.

[0135] In some embodiments, the surface of the first silicon-based material may have a carbon coating layer. For example, a carbon coating layer may be formed on the surface of elemental silicon, silicon oxide, etc., to improve the electronic conductivity of the first silicon-based material and reduce the powder resistivity. The powder resistivity of the first silicon-based material can be adjusted by adjusting parameters such as the thickness and graphitization degree of the carbon coating layer.

[0136] Of course, the surface of the first silicon-based material may not have a carbon coating layer. For example, the powder resistivity of the first silicon-based material can be adjusted by regulating parameters such as the structure and carbon content of the silicon-carbon material.

[0137] The carbon coating on the surface of the first silicon-based material can be formed by chemical vapor deposition, pyrolysis, hydrothermal methods, etc.

[0138] In some embodiments, the first active material may further include a first carbon-based material, which can improve the electronic conductivity of the negative electrode film, thereby enabling the secondary battery to maintain good cycle performance while improving its fast charging performance and energy density.

[0139] In some embodiments, the surface of the first carbon-based material may not have a carbon coating layer.

[0140] In some embodiments, the first carbon-based material may include secondary particles formed by the aggregation of primary particles.

[0141] In some embodiments, the first carbon-based material may include secondary particles formed by the aggregation of primary particles, and the surface of the secondary particles does not have a carbon coating layer. At high areal density, the diffusion resistance of the ionic liquid phase is dominant, and the carbon coating layer has little effect on further improving the fast-charging performance of the first carbon-based material of the secondary particles; in addition, the main component of the carbon coating layer is amorphous carbon, which will also affect the cycle performance of the secondary battery.

[0142] In some embodiments, the proportion of the first carbon-based material in the secondary particles can be ≥65%, for example ≥67.5%, ≥70%, ≥72.5%, or ≥75%. In high-energy-density battery systems, the porosity of the first region of the negative electrode film is often low, making ion liquid-phase transport difficult. By including an appropriate proportion of secondary particles in the first carbon-based material, the pore structure of the first region of the negative electrode film can be improved, thereby reducing the difficulty of ion liquid-phase transport and enabling ions to be rapidly transported to the particle surface. In addition, the first carbon-based material of the secondary particles can provide more ion insertion channels, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase. This is conducive to further optimization of the fast-charging performance of the secondary battery.

[0143] Further research by the inventors revealed that the proportion of the first carbon-based material in the secondary particles should not be too high, as this would lead to more side reactions in the secondary battery, affecting its cycle performance. Optionally, in some embodiments, the proportion of the first carbon-based material in the secondary particles can be 65%-95%, 70%-95%, 75%-95%, 65%-90%, 70%-90%, 75%-90%, 65%-85%, 70%-85%, or 75%-85%. This allows the secondary battery to achieve both good fast-charging and cycle performance.

[0144] In some embodiments, the first carbon-based material may further include primary particles (referring to non-agglomerated particles), and the proportion of the primary particles in the first carbon-based material may be ≤35%.

[0145] In some embodiments, the surface of the first carbon-based material does not have a carbon coating layer, and the first carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first carbon-based material in the secondary particles is ≥65%. In high-energy-density battery systems, when the surface of the first carbon-based material particles of the secondary particles has a carbon coating layer, the compaction density difference between the second region and the first region of the negative electrode film is small, and the matching between the pore distribution and ion concentration distribution in the thickness direction of the negative electrode film deteriorates, resulting in a smaller improvement in the fast-charging performance of the secondary battery.

[0146] In some embodiments, the volumetric particle size Dv50 of the first carbon-based material can be 12-18 μm, optionally 14-16 μm. When the volumetric particle size Dv50 of the first carbon-based material is within the above range, it is beneficial to improve the transport performance of ions and electrons, thereby further improving the fast-charging performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the first carbon-based material, reduce side reactions, and thus further improve the cycle performance of the secondary battery.

[0147] The inventors further discovered that when the first carbon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as further improving at least one of the energy density, cycle performance, and fast charging performance of the secondary battery.

[0148] In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material can be 24-30 μm, and optionally 25-29 μm. When the volume distribution particle size Dv90 of the first carbon-based material is within the above range, the uniformity of the first carbon-based material particles is better, which is beneficial to improving the ion and electron transport performance, thereby further improving the fast charging performance of the secondary battery.

[0149] In some embodiments, the first carbon-based material satisfies (Dv90-Dv10) / Dv50 as 0.8-1.6, optionally 1.0-1.3. When (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, it is beneficial for the first region of the negative electrode film to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transport and further improving the fast charging performance of the secondary battery; in addition, the first carbon-based material also has good particle packing performance, which is beneficial to increasing the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0150] In some embodiments, the specific surface area of ​​the first carbon-based material may be 2.0-4.0 m². 2 / g, can be selected as 2.5-3.1m 2 / g. When the specific surface area of ​​the first carbon-based material is within the above-mentioned range, it can increase the ion insertion channels in the first region of the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the first carbon-based material is within the above-mentioned range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have good cycle performance.

[0151] In some embodiments, the powder compaction density of the first carbon-based material at 20000N can be 1.8-2.0 g / cm³. 3 The selectable value is 1.85-1.95 g / cm³. 3 When the compaction density of the first carbon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0152] In some embodiments, the tap density of the first carbon-based material may be 0.9-1.1 g / cm³. 3 The selectable value is 0.95-1.05 g / cm³. 3 When the tap density of the first carbon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the first region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0153] In some embodiments, the graphitization degree of the first carbon-based material may be ≥93%, and optionally 93%-95%. When the graphitization degree of the first carbon-based material is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film, thereby enabling the secondary battery to achieve both high energy density and good fast charging performance.

[0154] In some embodiments, the specific capacity of the first carbon-based material can be ≥355 mAh / g, optionally 357-364 mAh / g. When the specific capacity of the first carbon-based material is within the above range, it can improve the energy density of the secondary battery on the one hand, and on the other hand, it can also give the first carbon-based material good ion transport performance, thereby also helping to improve the fast charging performance of the secondary battery.

[0155] In some embodiments, the powder OI value of the first carbon-based material can be 3-10, preferably 5-8. A lower powder OI value of the first carbon-based material allows it to quickly receive ions from the positive electrode, thereby further improving the fast-charging performance of the secondary battery.

[0156] In some embodiments, the volumetric particle size Dv50 of the first carbon-based material is denoted as A, in μm, and the specific surface area of ​​the first carbon-based material is denoted as B, in m². 2 If the ratio is 4 / g, then A / B can be 4-11, or optionally 5-7. Adjusting A / B within this range increases the ion insertion channels in the negative electrode film, facilitating rapid diffusion of ions from the particle surface to the bulk phase, thus further optimizing the fast-charging performance of the secondary battery. Furthermore, it helps reduce side reactions, thereby enabling the secondary battery to have good cycle performance.

[0157] In some embodiments, the first carbon-based material may include graphite, and optionally, the graphite may include synthetic graphite.

[0158] In some embodiments, the first carbon-based material may include secondary particulate graphite. Optionally, the secondary particulate graphite accounts for ≥65% of the first carbon-based material, for example, ≥67.5%, ≥70%, ≥72.5%, or ≥75%. As an example, the secondary particulate graphite may account for 65%-95%, 70%-95%, 75%-95%, 65%-90%, 70%-90%, 75%-90%, 65%-85%, 70%-85%, or 75%-85%.

[0159] In some embodiments, the mass percentage of the first carbon-based material in the first active material may be ≥50%, and can be selected as 60%-98%, 70%-98%, 80%-98%, 85%-98%, 60%-97%, 70%-97%, 80%-97%, or 85%-97%. By adjusting the content of the first carbon-based material within the above range, the electronic conductivity of the negative electrode film can be improved, thereby enhancing the fast-charging performance of the secondary battery while ensuring good cycle performance.

[0160] The second region 1022 includes a second active material that is different from the first active material.

[0161] In some embodiments, the second active material comprises a second carbon-based material.

[0162] In some embodiments, the second carbon-based material may include secondary particles formed by the aggregation of primary particles. When the second carbon-based material includes secondary particles, it facilitates the rapid transport of ions to the particle surface; furthermore, the secondary carbon-based material can provide more ion insertion channels, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase. Thus, when the second carbon-based material includes secondary particles formed by the aggregation of primary particles, it is beneficial to further improve the fast-charging performance of the secondary battery and to achieve the goal of ultra-fast charging.

[0163] In some embodiments, the first active material includes a first carbon-based material, and the second active material includes a second carbon-based material. The first carbon-based material includes secondary particles formed by the aggregation of primary particles, and the second carbon-based material includes secondary particles formed by the aggregation of primary particles. The proportion of the second carbon-based material in the secondary particles is less than the proportion of the first carbon-based material in the first carbon-based material. Typically, the second region of the negative electrode film has higher porosity, making ion transport in the liquid phase easier than in the first region. By adjusting the proportion of the second carbon-based material in the secondary particles to be less than the proportion of the first carbon-based material in the first carbon-based material, it is beneficial to reduce side reactions and improve the cycle performance of the secondary battery.

[0164] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material, wherein the volume distribution particle size Dv50 of the second carbon-based material may be smaller than the volume distribution particle size Dv50 of the first carbon-based material. By making the volume distribution particle size Dv50 of the second carbon-based material smaller than the volume distribution particle size Dv50 of the first carbon-based material, a good compaction density difference can be achieved between the second region and the first region of the negative electrode film. This results in better matching between the pore distribution and ion concentration distribution in the thickness direction of the negative electrode film, which is beneficial for improving the wetting and retention characteristics of the negative electrode film with the electrolyte and for ion transport. Consequently, the secondary battery can achieve both good fast-charging performance and cycle performance.

[0165] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material, wherein the specific surface area of ​​the second carbon-based material may be smaller than that of the first carbon-based material. By making the specific surface area of ​​the second carbon-based material smaller than that of the first carbon-based material, it is beneficial to reduce side reactions, thereby enabling the secondary battery to achieve both good fast-charging performance and cycle performance.

[0166] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material. The powder compaction density of the second carbon-based material at 20000N can be less than that of the first carbon-based material at 20000N. By making the powder compaction density of the second carbon-based material at 20000N less than that of the first carbon-based material at 20000N, the second and first regions of the negative electrode film can have good pore distribution and better match the ion concentration distribution in the thickness direction of the negative electrode film, reducing the difficulty of ion liquid phase transport and improving the wetting and retention characteristics of the negative electrode film to the electrolyte. This enables the secondary battery to achieve both good fast-charging performance and cycle performance.

[0167] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material, wherein the tap density of the second carbon-based material may be greater than the tap density of the first carbon-based material. By making the tap density of the second carbon-based material greater than the tap density of the first carbon-based material, the second region of the negative electrode film can achieve both good fast-charging performance and high energy density.

[0168] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material, wherein the degree of graphitization of the second carbon-based material may be less than that of the first carbon-based material. The lower degree of graphitization of the second carbon-based material results in a larger interlayer spacing, which is beneficial for rapid ion insertion / extraction; the higher degree of graphitization of the first carbon-based material results in a higher specific capacity. Therefore, by adjusting the degree of graphitization of the second carbon-based material to be less than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good fast-charging performance.

[0169] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material, wherein the specific capacity of the second carbon-based material may be less than the specific capacity of the first carbon-based material. By adjusting the specific capacity of the second carbon-based material to be less than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good fast-charging performance.

[0170] In some embodiments, the first active material comprises a first carbon-based material, and the second active material comprises a second carbon-based material. The OI value of the powder of the second carbon-based material may be lower than that of the powder of the first carbon-based material. The second carbon-based material has a smaller OI value and ion insertion ports in all directions of its particles, thereby enabling it to quickly receive ions from the positive electrode. By adjusting the OI value of the second carbon-based material to be lower than that of the first carbon-based material, rapid ion insertion and extraction is facilitated, thereby enabling the secondary battery to have better fast-charging performance.

[0171] The inventors further discovered that when the second carbon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as further improving at least one of the energy density, cycle performance, and fast charging performance of the secondary battery.

[0172] In some embodiments, the proportion of the second carbon-based material in the secondary particles can be ≥60%, for example ≥62.5%, ≥65%, ≥67.5%, or ≥70%. When the second carbon-based material contains an appropriate proportion of secondary particles, it is beneficial to further improve the fast charging performance of the secondary battery and to achieve the goal of ultra-fast charging.

[0173] Further research by the inventors revealed that the proportion of the second carbon-based material in the secondary particles should not be too high, as this would lead to more side reactions in the secondary battery, affecting its cycle performance. Optionally, in some embodiments, the proportion of the second carbon-based material in the secondary particles can be 60%-90%, 60%-85%, 60%-80%, 60%-75%, 65%-90%, 65%-85%, 65%-80%, 65%-75%, 70%-90%, 70%-85%, 70%-80%, or 70%-75%. This is beneficial for the secondary battery to better balance good fast-charging performance and cycle performance.

[0174] In some embodiments, the second carbon-based material may further include primary particles (referring to non-agglomerated particles), and the proportion of the primary particles in the second carbon-based material may be ≤40%.

[0175] In some embodiments, the surface of the second carbon-based material may have a carbon coating layer. The second carbon-based material is located on the surface portion of the negative electrode film. In this case, the presence of the carbon coating layer can increase ion diffusion channels, thereby facilitating further optimization of the fast-charging performance of the secondary battery.

[0176] In some embodiments, more than 80% of the surface of the second carbon-based material is covered with a carbon coating layer; alternatively, 90%-100% of the surface of the second carbon-based material is covered with a carbon coating layer.

[0177] In some embodiments, the surface of the second carbon-based material may have a carbon coating layer, and the carbon coating layer includes hard carbon. Hard carbon has the advantage of large interlayer spacing, which can accelerate ion diffusion, thereby facilitating further optimization of the fast-charging performance of the secondary battery.

[0178] The carbon coating layer on the surface of the second carbon-based material can be formed by carbonizing an organic carbon source. The organic carbon source can be any carbon-containing material known in the art that is suitable for coating, such as one or more of coal tar pitch, petroleum pitch, phenolic resin, coconut shell, etc.

[0179] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material can be 10-17 μm, and optionally 13-15 μm.

[0180] In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material can be 18-26 μm, and optionally 21-25 μm.

[0181] When the volume distribution particle sizes Dv50 and Dv90 of the second carbon-based material are within the above range, it is beneficial to improve the transport performance of ions and electrons, thereby further improving the fast charging performance of the secondary battery.

[0182] In some embodiments, the second carbon-based material satisfies (Dv90-Dv10) / Dv50 as 0.6-1.4, optionally 0.8-1.2. When (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, it is beneficial for the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, thereby further improving the fast charging performance of the secondary battery; in addition, the second carbon-based material also has good particle packing performance, which is beneficial for increasing the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0183] In some embodiments, the specific surface area of ​​the second carbon-based material may be 1.5-3.0 m². 2 / g, can be selected as 1.8-2.5m 2 / g. When the specific surface area of ​​the second carbon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the second carbon-based material is within the above range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0184] In some embodiments, the powder compaction density of the second carbon-based material at 20000N can be 1.65-1.85 g / cm³. 3 The selectable value is 1.70-1.80 g / cm³. 3 When the compaction density of the second carbon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0185] In some embodiments, the tap density of the second carbon-based material may be 1.0-1.2 g / cm³. 3 The selectable value is 1.05-1.15 g / cm³. 3 When the tap density of the second carbon-based material is within the above-mentioned range, the tap density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0186] In some embodiments, the graphitization degree of the second carbon-based material may be ≥91%, and optionally 92%-94%. When the graphitization degree of the second carbon-based material is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film, thereby enabling the secondary battery to achieve both high energy density and good fast charging performance.

[0187] In some embodiments, the specific capacity of the second carbon-based material can be ≥352 mAh / g, optionally 355-359 mAh / g. When the specific capacity of the second carbon-based material is within the above range, it can improve the energy density of the secondary battery on the one hand, and on the other hand, it can also give the carbon-based material good ion transport performance, thereby also helping to improve the fast charging performance of the secondary battery.

[0188] In some embodiments, the powder OI value of the second carbon-based material can be 2-8, preferably 3-6. The lower powder OI value of the second carbon-based material allows it to quickly receive ions from the positive electrode, thereby further improving the fast-charging performance of the secondary battery.

[0189] In some embodiments, the volumetric particle size Dv50 of the second carbon-based material is denoted as C, in μm, and the specific surface area of ​​the second carbon-based material is denoted as D, in m². 2 If the C / D ratio is within the specified range (g), then the C / D ratio can be 3-9, with a possible value of 4-6. Adjusting the C / D ratio within this range increases the ion insertion channels in the negative electrode film, facilitating the rapid diffusion of ions from the surface of the second carbon-based material particles to the bulk phase, thus further optimizing the fast-charging performance of the secondary battery. Furthermore, it helps reduce side reactions, thereby improving the cycle performance of the secondary battery.

[0190] In some embodiments, the second carbon-based material may include graphite, and optionally, the graphite may include synthetic graphite.

[0191] In some embodiments, the second carbon-based material may include artificial graphite with secondary particles. Optionally, the proportion of the artificial graphite with secondary particles in the second carbon-based material may be ≥60%, for example ≥62.5%, ≥65%, ≥67.5%, or ≥70%. As an example, the proportion of the artificial graphite with secondary particles in the second carbon-based material may be 60%-90%, 60%-85%, 60%-80%, 60%-75%, 65%-90%, 65%-85%, 65%-80%, 65%-75%, 70%-90%, 70%-85%, 70%-80%, or 70%-75%.

[0192] In some embodiments, the second carbon-based material may include artificial graphite with secondary particles, and the surface of the artificial graphite has a carbon coating layer.

[0193] In some embodiments, the mass percentage of the second carbon-based material in the second active material may be ≥70%, optionally 70%-100%, 75%-100%, 80%-100%, 85%-100%, 70%-95%, 75%-95%, 80%-95%, or 85%-95%. This is beneficial for improving the fast-charging performance of the secondary battery.

[0194] In some embodiments, the second carbon-based material may constitute 100% of the mass of the second active material.

[0195] In some embodiments, the second active material may include a second silicon-based material in addition to a second carbon-based material, thereby further improving the energy density of the secondary battery.

[0196] In some embodiments, the second silicon-based material may include one or more of primary particles and secondary particles formed by the aggregation of primary particles, and optionally may include primary particles.

[0197] In some embodiments, the second silicon-based material comprises primary particles, and the proportion of the second silicon-based material containing the primary particles in the second silicon-based material can be ≥60%, optionally 65%-95%. When the second silicon-based material is mainly composed of primary particles, it is beneficial to reduce the probability of particle breakage, increase the compaction density of the negative electrode film, and thus further improve the energy density of the secondary battery.

[0198] In some embodiments, the second silicon-based material may further include secondary particles, and the proportion of the secondary particles in the second silicon-based material may be ≤40%. The specific types of the primary particles and the secondary particles may be the same or different.

[0199] In some embodiments, the mass percentage of the second silicon-based material in the second active material may be less than the mass percentage of the first silicon-based material in the first active material. The second silicon-based material is in direct contact with the electrolyte. By making the mass percentage of the second silicon-based material in the second active material less than the mass percentage of the first silicon-based material in the first active material, side reactions can be reduced, thereby contributing to better cycle performance of the secondary battery.

[0200] In some embodiments, the volume distribution particle size Dv50 of the second silicon-based material can be smaller than that of the first silicon-based material. During the fabrication of the negative electrode, the second silicon-based material is more significantly affected by the pressure rollers, making its particles more prone to breakage. By adjusting the volume distribution particle size Dv50 of the second silicon-based material to be smaller than that of the first silicon-based material, the probability of particle breakage can be reduced, the electronic conductivity of the second silicon-based material can be increased, and the ion insertion channels of the negative electrode film can be increased. This allows the secondary battery to achieve both high energy density and good fast-charging performance.

[0201] In some embodiments, the specific surface area of ​​the second silicon-based material may be smaller than that of the first silicon-based material. When the specific surface area of ​​the second silicon-based material is smaller than that of the first silicon-based material, it is beneficial to reduce side reactions, thereby contributing to better cycle performance of the secondary battery.

[0202] In some embodiments, the powder compaction density of the second silicon-based material at 50,000 N can be greater than that of the first silicon-based material at 50,000 N. By adjusting the powder compaction density of the second silicon-based material to be greater than that of the first silicon-based material, it is beneficial to improve the energy density and cycle performance of the secondary battery.

[0203] In some embodiments, the tap density of the second silicon-based material may be greater than that of the first silicon-based material. By adjusting the tap density of the second silicon-based material to be greater than that of the first silicon-based material, it is beneficial to improve the energy density and cycle performance of the secondary battery.

[0204] In some embodiments, the powder resistivity of the second silicon-based material at 4 MPa may be lower than that of the first silicon-based material at 4 MPa. By adjusting the powder resistivity of the second silicon-based material to be lower than that of the first silicon-based material, it is beneficial to improve the electronic conductivity of the negative electrode film, thereby further improving the fast-charging performance of the secondary battery.

[0205] The inventors further discovered that when the second silicon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as further improving at least one of the energy density, cycle performance, and fast charging performance of the secondary battery.

[0206] In some embodiments, the volume distribution particle size Dv50 of the second silicon-based material can be 4-12 μm, and optionally 5-11 μm.

[0207] In some embodiments, the volume distribution particle size Dv90 of the second silicon-based material can be 8-18 μm, and optionally 9-17 μm.

[0208] When the volume distribution particle size Dv50 and / or Dv90 of the second silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film layer, which is conducive to the rapid diffusion of ions from the particle surface to the bulk phase, thereby facilitating further optimization of the fast charging performance of the secondary battery; at the same time, it can also reduce the risk of particle breakage of the second silicon-based material.

[0209] In some embodiments, the second silicon-based material satisfies that (Dv90-Dv10) / Dv50 can be 0.7-1.3, and optionally 0.8-1.2. When (Dv90-Dv10) / Dv50 of the second silicon-based material is within the above range, it is beneficial for the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, thereby further improving the fast charging performance of the secondary battery; in addition, the second silicon-based material can also have good particle packing performance, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery.

[0210] In some embodiments, the specific surface area of ​​the second silicon-based material may be 0.6-1.6 m². 2 / g, selectable from 0.7-1.5m 2 / g. When the specific surface area of ​​the second silicon-based material is within the above range, it can increase the ion insertion channels in the negative electrode film, which is beneficial for the rapid diffusion of ions from the particle surface to the bulk phase, thereby further optimizing the fast-charging performance of the secondary battery. In addition, when the specific surface area of ​​the second silicon-based material is within the above range, it is beneficial to reduce side reactions, thereby enabling the secondary battery to have better cycle performance.

[0211] In some embodiments, the powder compaction density of the second silicon-based material at 50000 N can be 1.2-1.8 g / cm³. 3 The concentration can be selected as 1.3-1.7 g / cm³. 3 When the compaction density of the second silicon-based material powder is within the above-mentioned range, the compaction density of the negative electrode film can be increased, thereby further improving the energy density of the secondary battery. It also helps the second region of the negative electrode film to have a suitable pore structure, reducing the difficulty of ion liquid phase transport, improving ion and electron transport performance, and improving the wetting and retention characteristics of the negative electrode film to the electrolyte, thereby further improving the fast charging performance and / or cycle performance of the secondary battery.

[0212] In some embodiments, the tap density of the second silicon-based material may be 1.1-1.7 g / cm³. 3 The concentration can be selected as 1.2-1.6 g / cm³. 3. When the tap density of the second silicon-based material falls within the above range, the compaction density of the negative electrode film layer can be increased, and the energy density of the secondary battery can be improved; it is also conducive to the second region of the negative electrode film layer having a suitable pore structure, thereby further reducing the difficulty of ionic liquid phase transmission, improving ion and electron transmission performance, enhancing the infiltration and retention characteristics of the negative electrode film layer for electrolyte, and thus further improving the fast charging performance and / or cycle performance of the secondary battery.

[0213] In some embodiments, the powder resistivity of the second silicon-based material at 4 MPa may be ≤5 Ω·cm, optionally 0.3-4 Ω·cm. When the powder resistivity of the second silicon-based material is adjusted within the above range, the electronic conductivity of the negative electrode film layer can be improved, and the fast charging performance of the secondary battery can be further enhanced.

[0214] In some embodiments, the mass proportion of the second silicon-based material in the second active material may be ≤30%, optionally ≤20%, ≤15%, or ≤10%. When the content of the second silicon-based material is adjusted within the above range, the secondary battery can achieve both good cycle performance while improving the fast charging performance and energy density of the secondary battery.

[0215] In some embodiments, the second silicon-based material may include elemental silicon, silicon oxide (SiO x , 0<x≤2), one or more of silicon-carbon materials and silicon alloy materials. The present application does not impose specific restrictions on the structure of the silicon-carbon material. For example, nano-silicon can be dispersed in carbon materials by high-energy ball milling, nano-silicon can be dispersed in porous carbon, carbon materials can be dispersed in porous silicon, carbon materials can be coated on the surface of nano-silicon, or nano-silicon and nano-carbon can be co-deposited together, etc.

[0216] In some embodiments, the surface of the second silicon-based material may be provided with a carbon coating layer. For example, a carbon coating layer may be provided on the surface of elemental silicon, silicon oxide, etc., to improve the electronic conductivity of the second silicon-based material and reduce the powder resistivity. The powder resistivity of the second silicon-based material can be adjusted by adjusting parameters such as the thickness and graphitization degree of the carbon coating layer.

[0217] Of course, the surface of the second silicon-based material may also not have a carbon coating layer. For example, the powder resistivity of the second silicon-based material can be adjusted by adjusting parameters such as the structure of the silicon-carbon material and the content of carbon element.

[0218] The carbon coating layer on the surface of the second silicon-based material can be formed by chemical vapor deposition, pyrolysis, hydrothermal method, etc.

[0219] In some embodiments, the first active material includes a first silicon-based material and a first carbon-based material; the first silicon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first silicon-based material in the secondary particles is ≥55%, optionally 60%-85%; the surface of the first carbon-based material does not have a carbon coating layer, and the first carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first carbon-based material in the secondary particles is ≥65%, optionally 70%-95%.

[0220] In some embodiments, the first active material includes a first silicon-based material and a first carbon-based material; the first silicon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first silicon-based material in the secondary particles is ≥55%, optionally 60%-85%; the surface of the first carbon-based material does not have a carbon coating layer, and the first carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first carbon-based material in the secondary particles is ≥65%, optionally 70%-95%; the second active material includes a second carbon-based material, which includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the second carbon-based material in the secondary particles is less than the proportion of the first carbon-based material in the secondary particles.

[0221] In some embodiments, the first active material includes a first silicon-based material and a first carbon-based material; the first silicon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first silicon-based material in the secondary particles is ≥55%, optionally 60%-85%; the surface of the first carbon-based material does not have a carbon coating layer, and the first carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the first carbon-based material in the secondary particles is ≥65%, optionally 70%-95%; the second active material includes a second carbon-based material and a second silicon-based material; the second carbon-based material includes secondary particles formed by the aggregation of primary particles, wherein the proportion of the second carbon-based material in the secondary particles is less than the proportion of the first carbon-based material in the secondary particles; the second silicon-based material includes primary particles, wherein the proportion of the second silicon-based material in the primary particles is ≥60%, optionally 65%-95%; the mass proportion of the second silicon-based material in the second active material is less than the mass proportion of the first silicon-based material in the first active material.

[0222] like Figures 1 to 3As shown, the negative electrode film layer 102 also includes an intermediate region 1023 located between the first region 1021 and the second region 1022 of the negative electrode film layer, with a thickness of 0.4H (H represents the thickness of the negative electrode film layer 102).

[0223] In some embodiments, the intermediate region 1023 includes a first active material and / or a second active material. For example, such as... Figure 2 As shown, the intermediate region 1023 can be composed of the same material as the first region 1021. Therefore, the distribution area of ​​the first active material in the thickness direction of the negative electrode film 102 is within a thickness range from the second surface 102b of the negative electrode film to 0.7H; or, as... Figure 3 As shown, the intermediate region 1023 can be composed of the same material as the second region 1022. Therefore, the distribution area of ​​the second active material in the thickness direction of the negative electrode film 102 is within a thickness range from the first surface 102a of the negative electrode film to 0.7H; or, as shown... Figure 1 As shown, the intermediate region 1023 includes both a first active material and a second active material. In this case, the intermediate region 1023 includes both a layer structure having the first active material and a layer structure having the second active material. The two layer structures may also have a layer interface.

[0224] In some embodiments, the first region 1021 of the negative electrode film may further include other negative electrode active materials known in the art besides the first carbon-based material and the first silicon-based material described above, such as one or more of tin-based materials, lithium titanate, etc.

[0225] In some embodiments, the second region 1022 of the negative electrode film may further include other negative electrode active materials known in the art besides the second carbon-based material and the second silicon-based material described above, such as one or more of tin-based materials, lithium titanate, etc.

[0226] In some embodiments, the middle region 1023 of the negative electrode film may also include one or more of tin-based materials, lithium titanate, etc.

[0227] In some embodiments, the first region, the second region, and the intermediate region of the negative electrode film may optionally include a negative electrode conductive agent and / or a negative electrode binder.

[0228] This application does not impose any particular limitation on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0229] This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0230] In some embodiments, the first region, the second region, and the intermediate region of the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.

[0231] In some embodiments, the porosity of the negative electrode film can be ≥18%, optionally 25%-45%. This is beneficial for the negative electrode film to achieve both high capacity and suitable pore structure, which in turn is beneficial for the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0232] In some embodiments, the compaction density of the negative electrode film layer may be ≥1.5 g / cm³. 3 The selectable value is 1.6-1.8 g / cm³. 3 This allows the negative electrode film to achieve both high capacity and good ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0233] In some embodiments, the areal density of the negative electrode film may be ≥7 mg / cm³. 2 12-30 mg / cm³ is an option. 2 This allows the negative electrode film to achieve both high capacity and good ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and fast charging performance.

[0234] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0235] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode film layer.

[0236] The negative electrode current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of these opposing surfaces. It should be noted that the negative electrode film layer parameters (e.g., compacted density, areal density, porosity, etc.) given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. When the negative electrode film layer is disposed on both sides of the negative electrode current collector, if the parameters of the negative electrode film layer on either side satisfy those of this application, it is considered to fall within the protection scope of this application.

[0237] Whether a carbon coating layer exists on the surface of a material (such as a first carbon-based material, a second carbon-based material, a first silicon-based material, a second silicon-based material, etc.) can be determined by transmission electron microscopy.

[0238] Primary particles and secondary particles are both well-known terms in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to aggregated particles formed by the aggregation of two or more primary particles. Primary and secondary particles can be distinguished using scanning electron microscopy (SEM) images.

[0239] The volumetric particle sizes Dv10, Dv50, and Dv90 of materials (e.g., first carbon-based materials, second carbon-based materials, first silicon-based materials, second silicon-based materials, etc.) are known in the art, representing the particle size corresponding to a cumulative volumetric distribution percentage of 10%, 50%, and 90%, respectively, and can be determined using instruments and methods known in the art. For example, they can be determined using a laser particle size analyzer, referring to GB / T 19077-2016. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0240] The specific surface area of ​​a material (e.g., a first carbon-based material, a second carbon-based material, a first silicon-based material, a second silicon-based material, etc.) has a well-known meaning in the art and can be determined using instruments and methods known in the art. For example, it can be tested using the nitrogen adsorption specific surface area analysis method according to GB / T19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.

[0241] The compacted density of powder (e.g., first carbon-based material, second carbon-based material, first silicon-based material, second silicon-based material, etc.) has a well-known meaning in the art and can be determined using instruments and methods known in the art. For example, it can be determined using an electronic pressure testing machine (e.g., a UTM7305 type electronic pressure testing machine) according to GB / T 24533-2009. An exemplary test method is as follows: Weigh 1g of sample powder and add it to a container with a bottom area of ​​1.327cm². 2 In the mold, pressurize to the required pressure, hold the pressure for 30 seconds, then release the pressure, hold for 10 seconds, and then record and calculate the compaction density of the powder material under the required pressure.

[0242] The tap density of materials (e.g., first carbon-based material, second carbon-based material, first silicon-based material, second silicon-based material, etc.) has a well-known meaning in the art and can be determined using instruments and methods known in the art. For example, it can be determined using a powder tap density tester according to GB / T5162-2006. The testing instrument can be Dandong Baite BT-301, with the following test parameters: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, number of vibrations 5000 times, and a 25mL graduated cylinder.

[0243] The degree of graphitization of materials (e.g., first carbon-based materials, second carbon-based materials, etc.) is a well-known concept in the art and can be tested using instruments and methods known in the art. For example, it can be tested using an X-ray diffractometer (such as a Bruker D8 Discover), and the testing can be performed in accordance with JIS K 0131-1996 and JB / T 4220-2011, to obtain the average interlayer spacing d of the C(002) crystal plane in the material's crystal structure. 002 Then, according to the formula g = (0.344 - d) 002 The degree of graphitization is calculated as d / (0.344-0.3354)×100%. In the above formula, d... 002 It is the average interlayer spacing of the C(002) crystal plane in the material crystal structure, expressed in nanometers (nm).

[0244] The OI value of a powder material (e.g., a first carbon-based material, a second carbon-based material, etc.) has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as a Bruker D8 Discover) can be used for testing, and the testing can be performed with reference to JIS K 0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction pattern of the powder sample. The OI value is calculated according to the formula: OI = I 004 / I 110 The OI value of the powder in the sample was calculated. 004 I is the integrated area of ​​the diffraction peak of the crystalline carbon 004 crystal plane in the powder sample.110 This represents the integrated area of ​​the diffraction peak on the 110 crystal plane of crystalline carbon in the powder sample. In the X-ray diffraction analysis of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the ray wavelength... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min.

[0245] The powder resistivity of a material (e.g., a first silicon-based material, a second silicon-based material, etc.) has a meaning known in the art and can be tested using instruments and methods known in the art. For example, a resistivity meter (such as the ST2722 powder resistivity meter from Suzhou Jingge Electronics Co., Ltd.) can be used. During testing, a 1g powder sample is placed between the electrodes of the resistivity meter, and a constant pressure (e.g., 4 MPa) is applied using an electronic pressure gauge for 15-25 seconds to obtain a sheet-like sample. The powder resistivity δ of the material is calculated using the formula δ=(S×R) / h, with units of Ω·cm. h is the height of the sheet-like sample in cm; R is the resistance in Ω; and S is the area of ​​the sheet-like sample in cm². 2 .

[0246] The specific capacity of materials (e.g., first carbon-based materials, second carbon-based materials, etc.) has a meaning known in the art and can be tested using methods known in the art. An exemplary test method is as follows: Sample powder is mixed with conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) at a mass ratio of 91.6:1.8:6.6 with solvent N-methylpyrrolidone (NMP) to form a slurry; the prepared slurry is coated onto the surface of the negative electrode current collector copper foil and dried in an oven for later use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a solution with a concentration of 1 mol / L. The electrolyte was prepared; then, using a lithium metal sheet as the counter electrode and a polyethylene (PE) film as the separator, the CR2430 coin cell was assembled with the electrolyte in an argon-protected glove box. After the coin cell was left to stand for 12 hours, it was discharged at 25°C with a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged again with a constant current of 50μA to 0.005V. After standing for 10 minutes, it was discharged again with a constant current of 10μA to 0.005V. Then, it was charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the sample mass is the specific capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, etc.).

[0247] The areal density of the negative electrode film is a term known in the art and can be tested using methods known in the art. For example, a negative electrode sheet coated on one side and cold-pressed (if it is a double-sided coated negative electrode sheet, the negative electrode film on one side can be wiped off first) can be cut into small circular pieces with an area of ​​S1, weighed, and recorded as M1. Then, the negative electrode film on the weighed negative electrode sheet is wiped off, and the weight of the negative current collector is weighed and recorded as M0. The areal density of the negative electrode sheet = (M1 - M0) / S1.

[0248] The compaction density of the negative electrode film is a term known in the art and can be tested using methods known in the art. The compaction density of the negative electrode film = the areal density of the negative electrode film / the thickness of the negative electrode film. The thickness of the negative electrode film is a term known in the art and can be tested using methods known in the art, such as a micrometer (e.g., a Mitutoyo 293-100 model with an accuracy of 0.1 μm).

[0249] The porosity of the negative electrode film is a well-known concept in the art and can be determined using methods known in the art. An exemplary test method is as follows: Take a negative electrode sheet coated on one side and cold-pressed (if it is a double-sided coated negative electrode sheet, the negative electrode film layer on one side can be wiped off first), cut it into small circular samples of a certain area, and calculate the apparent volume V1 of the negative electrode sheet; referring to GB / T24586-2009, using an inert gas (such as helium or nitrogen) as the medium, employ the gas displacement method and use a true density meter to measure the true volume V2 of the negative electrode sheet. The porosity of the negative electrode film = (V1-V2) / V1×100%. Multiple negative electrode sheet samples (e.g., 30 sheets) with good appearance and no powder shedding at the edges can be tested, and the average value of the results is taken, thereby improving the accuracy of the test results. The testing instrument can be a Micromeritics AccuPyc II 1340 true density meter.

[0250] The porosity of the primary silicon-based material with secondary particles can be determined using methods known in the art. For example, the true density ρ of the primary silicon-based material with secondary particles can be obtained by measuring a true density meter (e.g., AccuPycⅡ1340). r Specifically, the process may include the following steps: Weigh a sample of a certain mass (denoted as m), place it in a true density tester, seal the test system, and introduce helium gas according to the procedure; by detecting the gas pressure in the sample chamber and expansion chamber, and then calculating the true volume V of the first silicon-based material of the secondary particles according to Bohr's Law (PV = nRT). r The true density ρ of the first silicon-based material of the secondary particles is... r =m / V rThe apparent density of the secondary particle-based silicon material can be obtained by loading a sample of a certain mass (denoted as m) into a cylindrical mold with an inner diameter of 10 mm and applying a pressure of 200 MPa. The apparent volume V0 of the secondary particle-based silicon material is then calculated as ρ0 = m / V0. The porosity of the secondary particle-based silicon material is denoted as P, and P = (1 - ρ0 / ρ r )×100%.

[0251] It should be noted that the above-mentioned tests on various parameters of the first active material, the second active material, or the negative electrode film can be performed by sampling and testing from the prepared secondary battery according to the following steps.

[0252] The secondary battery is discharged (for safety, it is generally left fully discharged); after disassembling the secondary battery, the negative electrode is removed and soaked in dimethyl carbonate for a certain period of time (e.g., 2-10 hours); then the negative electrode is removed and dried at a certain temperature and time (e.g., 60°C for more than 4 hours), and then the negative electrode is removed. At this point, samples can be taken from the dried negative electrode to test the parameters related to the negative electrode film, such as the areal density, compaction density, and porosity of the negative electrode film.

[0253] The dried negative electrode sheet is baked at a certain temperature and time (e.g., 400℃ for more than 2 hours). Select a region in the baked negative electrode sheet and take a sample of the second active material (a blade can be used to scrape the powder for sampling). The sampling location is the second region of the negative electrode film. Then, take a sample of the first active material in the same way. The sampling location is the first region of the negative electrode film. The collected first and second active materials are sieved (e.g., sieved through a 200-mesh sieve) to finally obtain the first and second active material samples that can be used to test the material parameters of the present application.

[0254] As an example, the method for testing the proportion of the first silicon-based material in the secondary particles can be as follows: The first active material obtained above is laid and adhered to conductive adhesive to form a 6cm × 1.1cm sample to be tested; the particle morphology is tested using a scanning electron microscope, referring to JY / T010-1996. To ensure the accuracy of the test results, multiple (e.g., 10) different regions can be randomly selected from the sample to be tested for scanning. At a certain magnification (e.g., 500x or 1000x), the ratio of the number of the first silicon-based material in the secondary particles to the total number of the first silicon-based material in each test region is calculated, and the average of the calculated results from multiple test regions is taken as the test result. To ensure the accuracy of the test results, multiple test samples (e.g., 5 or 10) can be prepared and the above test can be repeated, and the average of each test sample is taken as the final test result. Similarly, the proportion of the first carbon-based material in the secondary particles can also be tested.

[0255] As an example, the method for testing the proportion of the secondary carbon-based material in the secondary particles can be as follows: The obtained secondary active material is laid and adhered to conductive adhesive to form a 6cm × 1.1cm sample. The particle morphology is tested using a scanning electron microscope (SEM), referring to JY / T010-1996. To ensure the accuracy of the test results, multiple (e.g., 10) different regions can be randomly selected from the sample for scanning. At a certain magnification (e.g., 500x or 1000x), the ratio of the number of secondary carbon-based materials in each test region to the total number of secondary carbon-based materials is calculated, and the average of the calculated results from multiple test regions is taken as the test result. To ensure the accuracy of the test results, multiple test samples (e.g., 5 or 10) can be prepared and the above test repeated, with the average of each test sample taken as the final test result. Similarly, the proportion of the secondary silicon-based material in the primary particles can also be tested.

[0256] The ratio of primary particles (referring to non-agglomerated particles) to secondary particles in the aforementioned carbon-based material (e.g., the first carbon-based material or the second carbon-based material) can be adjusted using methods known in the art. For example, when the carbon-based material is graphite, the ratio of primary to secondary particles can be adjusted by regulating preparation parameters (e.g., type of coke raw material, shaping process, granulation process, type and amount of granulating agent, etc.); alternatively, the ratio of primary to secondary particles can be adjusted by regulating the mixing ratio of primary and secondary graphite particles.

[0257] The ratio of primary particles (referring to non-agglomerated particles) to secondary particles in silicon-based materials (such as the first silicon-based material or the second silicon-based material) can be adjusted in a similar way. For example, the ratio of primary to secondary particles can be adjusted by regulating preparation parameters (such as the type of raw materials, granulation process, type and amount of granulating agent, etc.); or the ratio of primary to secondary particles can be adjusted by regulating the mixing ratio of the silicon-based material in the primary particles to the silicon-based material in the secondary particles.

[0258] [Preparation method of negative electrode sheet]

[0259] This application also provides a method for preparing the negative electrode sheet of this application. The method includes the following steps: providing a first slurry containing a first active material and a second slurry containing a second active material; coating the first slurry onto a negative current collector, coating the second slurry onto the first slurry, and obtaining the negative electrode sheet after drying and cold pressing.

[0260] In some embodiments, the first active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a first slurry.

[0261] In some embodiments, the second active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a second slurry.

[0262] In some embodiments, the first active material may include a first silicon-based material, or a mixture of a first silicon-based material and a first carbon-based material.

[0263] In some embodiments, the second active material may include a second carbon-based material, or a mixture of a second carbon-based material and a second silicon-based material.

[0264] The first and second slurries can be coated simultaneously or separately. In some embodiments, the first and second slurries are coated simultaneously. Simultaneous coating can reduce the negative electrode film resistance, thereby further improving the fast-charging and cycle performance of the secondary battery.

[0265] The coating weights of the first and second slurries can be adjusted according to actual conditions.

[0266] The first active material, the second active material, etc. mentioned above can be obtained commercially or prepared by the method described in this application.

[0267] In some embodiments, the silicon-based material containing secondary particles can be prepared by preparing a solution comprising primary particles, a binder, and a solvent, and then spray-drying the solution to obtain the silicon-based material containing secondary particles. The binder is not particularly limited, and specific examples may include one or more of asphalt, starch, phenolic resin, polyvinyl alcohol, epoxy resin, chlorinated polyvinyl resin, butyl rubber, etc. The solvent is not particularly limited, as long as it sufficiently disperses the primary particles; specific examples may include one or more of water, alcohol, N-methylpyrrolidone (NMP), dimethyl sulfoxide, acetonitrile, acetone, tetrahydrofuran, diethyl ether, toluene, 1,2-dichlorobenzene, etc. The spray-drying temperature can be between 100°C and 250°C.

[0268] Alternatively, the secondary particle-based material can be prepared by mixing primary particles with a binder and granulating the mixture, followed by heat treatment to obtain a silicon-based material containing secondary particles. The binder is not particularly limited, and specific examples may include one or more of the following: asphalt, starch, phenolic resin, polyvinyl alcohol, epoxy resin, chlorinated polyvinyl chloride resin, butyl rubber, etc.

[0269] The porosity of the secondary particle-based material can be adjusted to a suitable range by regulating the aggregation. Specifically, the secondary particles can be immersed in a high-temperature molten filler, the filler filling degree can be controlled by pressure, and then high-temperature carbonization can be performed to adjust the porosity. Specific examples of fillers may include one or more of the following: asphalt, starch, phenolic resin, polyvinyl alcohol, epoxy resin, chlorinated polyvinyl chloride resin, butyl rubber, and polymethyl methacrylate.

[0270] When preparing silicon-based materials with secondary particles, the types of primary particles used can be the same or different.

[0271] In some embodiments, primary particulate carbon-based materials can be prepared by crushing and shaping coke raw materials, followed by graphitization treatment, to obtain primary particulate carbon-based materials. Specific examples of coke raw materials may include one or more of petroleum coke, needle coke, pitch coke, and metallurgical coke. The graphitization temperature may be between 2800°C and 3200°C.

[0272] In some embodiments, the carbon-based material containing secondary particles can be prepared by crushing and shaping a coke feedstock, then mixing it with a binder for granulation, followed by graphitization treatment, to obtain a carbon-based material containing secondary particles. Specific examples of the coke feedstock may include one or more of petroleum coke, needle coke, pitch coke, and metallurgical coke. The graphitization temperature may be between 2800°C and 3200°C. Specific examples of the binder may include pitch.

[0273] The above-described preparation process does not include the step of forming a carbon coating layer on the material surface. As an example, the carbon coating layer on the surface of a carbon-based material can be formed by carbonizing an organic carbon source. The organic carbon source can be any carbon-containing material known in the art suitable for coating, such as one or more of coal tar pitch, petroleum pitch, phenolic resin, and coconut shell. The carbon coating layer on the surface of a silicon-based material can be formed by chemical vapor deposition, pyrolysis, hydrothermal methods, etc.

[0274] [Positive electrode plate]

[0275] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0276] The positive electrode current collector can be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil can be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0277] The positive electrode film typically comprises a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film is typically formed by coating a positive electrode slurry onto the positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring until homogeneous. The solvent may be N-methylpyrrolidone (NMP), but is not limited to this. As an example, the binder used for the positive electrode film may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. As an example, the conductive agent used for the positive electrode film includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0278] The positive electrode active material may be a positive electrode active material known in the art for use in secondary batteries.

[0279] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material for the lithium-ion battery may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates, and modified compounds thereof respectively. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof respectively. Examples of the lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, composite materials of lithium iron phosphate and carbon, lithium manganese phosphate, composite materials of lithium manganese phosphate and carbon, lithium manganese iron phosphate, composite materials of lithium manganese iron phosphate and carbon, and modified compounds thereof respectively.

[0280] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material for a lithium-ion battery may include a lithium transition metal oxide with the general formula Li a Ni b Co c M d O e A f and one or more of modified compounds thereof. Wherein 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.

[0281] In some embodiments, by way of example, the positive electrode active material for a lithium-ion battery may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4 and LiMnPO4, one or more of which.

[0282] The modified compound of each of the above positive electrode active materials may be obtained by doping modification and / or surface coating modification on the positive electrode active material.

[0283] [Electrolytes]

[0284] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0285] The type of electrolyte salt is not specifically limited and can be selected according to actual needs.

[0286] When the secondary battery of this application is a lithium-ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0287] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0288] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain performance characteristics of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high-temperature performance of the secondary battery, and additives that improve the low-temperature power performance of the secondary battery.

[0289] [Isolation membrane]

[0290] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.

[0291] In some embodiments, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.

[0292] In some embodiments, the positive electrode, the separator, and the negative electrode can be fabricated into an electrode assembly using a winding process or a stacking process.

[0293] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0294] In some embodiments, the outer packaging may be a hard shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging may also be a flexible package, such as a pouch. The material of the flexible package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0295] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 4 This is an example of a square-structured secondary battery 5.

[0296] In some embodiments, such as Figure 5 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.

[0297] The method for preparing the secondary battery described in this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding or stacking process. The electrode assembly is then placed in an outer packaging, dried, and injected with an electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0298] In some embodiments, the secondary battery according to this application can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module.

[0299] Figure 6This is a schematic diagram of battery module 4 as an example. Figure 6 As shown, in battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.

[0300] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.

[0301] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0302] Figure 7 and Figure 8 This is a schematic diagram of battery pack 1 as an example. Figure 7 and Figure 8 As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0303] This application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack described in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0304] The electrical device can be equipped with a secondary battery, battery module, or battery pack according to its usage requirements.

[0305] Figure 9 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0306] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.

[0307] Example

[0308] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0309] The first and second carbon-based materials in Comparative Example 1 are both primary particles that can be commercially available or prepared by the following method: after crushing and shaping petroleum coke, graphitization is carried out in the range of 2800℃ to 3200℃, and the product is obtained by sieving after cooling to room temperature.

[0310] In various embodiments, the first and second carbon-based materials can be commercially available or prepared by the following method: crushing and shaping petroleum coke, then mixing it with binder asphalt for granulation, followed by graphitization treatment at a temperature between 2800°C and 3200°C, and finally cooling to room temperature and sieving to obtain the product. The proportion of primary and secondary particles in the first (second) carbon-based material can be adjusted by regulating the preparation process parameters (e.g., shaping process, granulation process, asphalt type and dosage); the proportion of primary and secondary particles can also be adjusted by regulating the mixing ratio of the primary and secondary carbon-based materials.

[0311] In the following embodiments and comparative examples, the carbon coating layer on the surface of the first carbon-based material and the second carbon-based material can be formed by mixing the graphitized material with petroleum asphalt and then carbonizing it.

[0312] Both the first and second silicon-based materials in Comparative Example 1 are primary particles and are commercially available.

[0313] In the following embodiments, the first silicon-based material (second silicon-based material) of the secondary particles is commercially available, or it can be prepared by mixing the silicon-based material of the primary particles with binder pitch and then subjecting it to heat treatment. The ratio of primary to secondary particles can be adjusted by regulating preparation parameters (e.g., granulation process, type and amount of pitch); or the ratio of primary to secondary particles can be adjusted by regulating the mixing ratio of the commercially available silicon-based material of the primary particles and the commercially available silicon-based material of the secondary particles.

[0314] In the following embodiments and comparative examples, the carbon coating layer on the surface of the pre-lithium-intercalated silicon oxide can be formed by chemical vapor deposition.

[0315] The secondary batteries of Examples 1-17 and Comparative Example 1 were all prepared according to the following method.

[0316] The first active material (see Table 1), conductive agent Super P, carbon nanotubes (CNTs), binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose were thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 96.2:0.7:0.1:1.8:1.2 to form the first slurry. The sum of the proportion of secondary particles to primary particles in the first carbon-based material is 100%, and the sum of the proportion of secondary particles to primary particles in the first silicon-based material is also 100%. Therefore, the proportion of secondary particles or primary particles can be calculated from the proportion of primary particles or secondary particles in Table 1.

[0317] The second active material (see Table 2), conductive agent Super P, carbon nanotubes (CNTs), binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose were thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 96.2:0.7:0.1:1.8:1.2 to form a second slurry. The sum of the proportion of secondary particles to primary particles in the second carbon-based material is 100%, and the sum of the proportion of secondary particles to primary particles in the second silicon-based material is also 100%. Therefore, the proportion of secondary particles or primary particles can be calculated from the proportion of primary particles or secondary particles in Table 2.

[0318] A first slurry and a second slurry are simultaneously extruded using a dual-cavity coating apparatus. The first slurry is coated on both surfaces of the copper foil used as the negative electrode current collector, and the second slurry is coated on top of the first slurry. After drying and cold pressing, the negative electrode sheet is obtained. The coating weights of the first and second slurries are the same. The areal density of the negative electrode film layer on one side is 12.5 mg / cm³. 2 The compaction density of the negative electrode film layer on one side is 1.80 g / cm³. 3 .

[0319] LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent Super P, and binder polyvinylidene fluoride are mixed in a weight ratio of 96.5:1.5:2. An appropriate amount of solvent NMP is added, and the mixture is stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0320] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 was then dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0321] A PP / PE composite membrane is used as a separator. It is placed in sequence with the positive and negative electrode sheets prepared above, so that the separator is in the middle of the positive and negative electrode sheets to play a role in isolation. Then, the electrode assembly is wound to obtain the electrode assembly. The electrode assembly is placed in the outer packaging, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, aging and other processes, a secondary battery is obtained.

[0322] Table 1

[0323]

[0324] Table 2

[0325]

[0326]

[0327] Performance testing

[0328] (1) Fast charging performance test of secondary batteries

[0329] At 25°C, the secondary battery was charged to 4.3V at a constant current of 0.33C, then charged to 0.05C at a constant voltage. After standing for 5 minutes, the secondary battery was discharged to 2.8V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0330] Then, the secondary battery was sequentially charged at constant current rates of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, and 3.0C0 until it reached 4.3V or 0V negative terminal cutoff potential (whichever comes first). After each charge, it was discharged to 2.8V at 1C0. The state of charge (SOC) was recorded at different charging rates until it reached 10%, 20%, 30%, ..., 80%. By plotting the negative electrode potential corresponding to the state of charge (SOC), the charging rate-negative electrode potential curves under different SOC states are obtained. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. This charging rate is the charging window under that SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC, respectively. The charging time T (assuming no lithium plating in the secondary battery) from 10%SOC to 80%SOC is calculated according to the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, in minutes. The shorter the charging time, the better the fast charging performance of the secondary battery.

[0331] (2) Cycle performance test of secondary batteries

[0332] At 45℃, the prepared secondary battery was charged at a constant current of 1C to 4.3V, then charged at a constant voltage to a current of 0.05C. After standing for 5 minutes, the secondary battery was discharged at a constant current of 1C to 2.8V, and the discharge capacity at this point was recorded, which is the discharge capacity of the first cycle. The secondary battery was subjected to cyclic charge-discharge tests according to the above method, and the discharge capacity after each cycle was recorded. The capacity retention rate (%) of the secondary battery after 200 cycles at 45℃ = discharge capacity after 200 cycles / discharge capacity of the first cycle × 100%.

[0333] Table 3

[0334] Example 1 20.0 96.00% Example 2 19.0 95.20% Example 3 18.5 94.90% Example 4 21.5 96.50% Example 5 23.7 92.10% Example 6 20.2 93.50% Example 7 18.3 95.30% Example 8 20.9 96.20% Example 9 21.4 96.50% Example 10 24.1 91.50% Example 11 20.6 96.80% Example 12 20.1 94.20% Example 13 19.0 95.10% Example 14 21.2 90.70% Example 15 21.2 96.70% Example 16 20.7 91.10% Example 17 23.2 97.10% Comparative Example 1 30.0 90.00%

[0335] As can be seen from the test results in Table 3, the negative electrode sheet of this application can enable high energy density batteries to have good fast charging performance, as well as good cycle performance.

[0336] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A secondary battery, comprising a negative electrode, wherein, The negative electrode sheet includes a negative current collector and a negative electrode film layer. The negative electrode film layer is located on at least one side of the surface of the negative current collector. The negative electrode film layer has a first surface away from the negative current collector and a second surface disposed opposite to the first surface. The thickness of the negative electrode film layer is denoted as H. The region from the second surface of the negative electrode film layer to a thickness of 0.3 H is denoted as the first region of the negative electrode film layer, and the region from the first surface of the negative electrode film layer to a thickness of 0.3 H is denoted as the second region of the negative electrode film layer. The negative electrode film layer also includes an intermediate region located between the first region and the second region with a thickness of 0.4 H. The intermediate region includes a first active material and / or a second active material. The first region includes a first active material, and the second region includes a second active material. The first active material comprises a first silicon-based material and a first carbon-based material. The first silicon-based material includes secondary particles formed by the aggregation of primary particles. The proportion of the first silicon-based material in the secondary particles is ≥55%. The first carbon-based material includes secondary particles formed by the aggregation of primary particles. The second active material includes a second carbon-based material and a second silicon-based material. The second carbon-based material includes secondary particles formed by the aggregation of primary particles. The proportion of the second carbon-based material in the secondary particles is ≥60%, and the proportion of the second carbon-based material in the secondary particles is less than the proportion of the first carbon-based material in the secondary particles. The second silicon-based material includes primary particles, and the proportion of the second silicon-based material in the primary particles is ≥60%.

2. The secondary battery according to claim 1, wherein, The proportion of the first silicon-based material in the secondary particles is 60%-85%.

3. The secondary battery according to claim 1, wherein, The surface of the first carbon-based material does not have a carbon coating layer.

4. The secondary battery according to claim 1, wherein, The proportion of the first carbon-based material in the secondary particles is ≥65%.

5. The secondary battery according to claim 4, wherein, The proportion of the first carbon-based material in the secondary particles is 70%-95%.

6. The secondary battery according to claim 1, wherein, The volume distribution particle size Dv50 of the first carbon-based material is 12-18 μm.

7. The secondary battery according to claim 6, wherein, The volumetric particle size Dv50 of the first carbon-based material is 14-16 μm.

8. The secondary battery according to claim 1, wherein, The first carbon-based material satisfies at least one of the following (1)-(11): (1) The volume distribution particle size Dv90 of the first carbon-based material is 24-30 μm; (2) The first carbon-based material satisfies (Dv90-Dv10) / Dv50 as 0.8-1.6; (3) The specific surface area of ​​the first carbon-based material is 2.0-4.0 m². 2 / g; (4) The compacted density of the first carbon-based material at 20000N is 1.8-2.0 g / cm³. 3 ; (5) The tap density of the first carbon-based material is 0.9-1.1 g / cm³. 3 ; (6) The degree of graphitization of the first carbon-based material is ≥93%; (7) The specific capacity of the first carbon-based material is ≥355mAh / g; (8) The OI value of the powder of the first carbon-based material is 3-10; (9) The volumetric particle size Dv50 of the first carbon-based material is denoted as A, with units of μm, and the specific surface area of ​​the first carbon-based material is denoted as B, with units of m². 2 / g, then A / B is 4-11; (10) The first carbon-based material includes graphite; (11) The mass percentage of the first carbon-based material in the first active material is ≥50%.

9. The secondary battery according to claim 8, wherein, The first carbon-based material satisfies at least one of the following (1)-(11): (1) The volume distribution particle size Dv90 of the first carbon-based material is 25-29 μm; (2) The first carbon-based material satisfies (Dv90-Dv10) / Dv50 as 1.0-1.3; (3) The specific surface area of ​​the first carbon-based material is 2.5-3.1 m². 2 / g; (4) The compacted density of the first carbon-based material at 20000N is 1.85-1.95 g / cm³. 3 ; (5) The tap density of the first carbon-based material is 0.95-1.05 g / cm³. 3 ; (6) The graphitization degree of the first carbon-based material is 93%-95%; (7) The specific capacity of the first carbon-based material is 357-364 mAh / g; (8) The OI value of the powder of the first carbon-based material is 5-8; (9) The volumetric particle size Dv50 of the first carbon-based material is denoted as A, with units of μm, and the specific surface area of ​​the first carbon-based material is denoted as B, with units of m². 2 / g, then A / B is 5-7; (10) The first carbon-based material includes artificial graphite; (11) The mass percentage of the first carbon-based material in the first active material is 60%-98%.

10. The secondary battery according to claim 1, wherein, The first carbon-based material and the second carbon-based material satisfy at least one of the following (1)-(7): (1) The volume distribution particle size Dv50 of the second carbon-based material is smaller than that of the first carbon-based material; (2) The specific surface area of ​​the second carbon-based material is smaller than that of the first carbon-based material; (3) The compacted density of the second carbon-based material at 20000N is less than that of the first carbon-based material at 20000N; (4) The tap density of the second carbon-based material is greater than that of the first carbon-based material; (5) The degree of graphitization of the second carbon-based material is less than that of the first carbon-based material; (6) The specific capacity of the second carbon-based material is less than that of the first carbon-based material; (7) The powder OI value of the second carbon-based material is less than that of the powder OI value of the first carbon-based material.

11. The secondary battery according to claim 1, wherein, The second carbon-based material satisfies at least one of the following (1)-(14): (1) The secondary particles account for 65%-90% of the amount of the second carbon-based material in the second carbon-based material; (2) The surface of the second carbon-based material has a carbon coating layer; (3) The volume distribution particle size Dv50 of the second carbon-based material is 10-17 μm; (4) The volume distribution particle size Dv90 of the second carbon-based material is 18-26 μm; (5) The second carbon-based material satisfies (Dv90-Dv10) / Dv50 of 0.6-1.4; (6) The specific surface area of ​​the second carbon-based material is 1.5-3.0 m². 2 / g; (7) The compacted density of the second carbon-based material at 20000N is 1.65-1.85 g / cm³. 3 ; (8) The tap density of the second carbon-based material is 1.0-1.2 g / cm³. 3 ; (9) The degree of graphitization of the second carbon-based material is ≥91%; (10) The specific capacity of the second carbon-based material is ≥352mAh / g; (11) The OI value of the second carbon-based material powder is 2-8; (12) The volumetric particle size Dv50 of the second carbon-based material is denoted as C, with units of μm, and the specific surface area of ​​the second carbon-based material is denoted as D, with units of m². 2 / g, then C / D is 3-9; (13) The second carbon-based material includes graphite; (14) The mass percentage of the second carbon-based material in the second active material is ≥70%.

12. The secondary battery according to claim 11, wherein, The surface of the second carbon-based material has a carbon coating layer, the carbon coating layer comprising hard carbon; The volume distribution particle size Dv50 of the second carbon-based material is 13-15 μm; The volumetric particle size Dv90 of the second carbon-based material is 21-25 μm; The second carbon-based material satisfies (Dv90-Dv10) / Dv50 of 0.8-1.2; The specific surface area of ​​the second carbon-based material is 1.8-2.5 m². 2 / g; The second carbon-based material has a powder compaction density of 1.70-1.80 g / cm³ at 20000 N. 3 ; The tap density of the second carbon-based material is 1.05-1.15 g / cm³. 3 ; The graphitization degree of the second carbon-based material is 92%-94%; The specific capacity of the second carbon-based material is 355-359 mAh / g; The OI value of the second carbon-based material powder is 3-6; The volumetric particle size Dv50 of the second carbon-based material is denoted as C, in μm, and the specific surface area of ​​the second carbon-based material is denoted as D, in m². 2 / g, then C / D is 4-6; The second carbon-based material includes graphite, wherein the graphite includes synthetic graphite; The second carbon-based material accounts for 75%-95% of the mass of the second active material.

13. The secondary battery according to claim 1, wherein, The first silicon-based material satisfies at least one of the following (1)-(10): (1) The porosity of the first silicon-based material of the secondary particles is ≥4%; (2) The volume distribution particle size Dv50 of the first silicon-based material is 8-15 μm; (3) The volume distribution particle size Dv90 of the first silicon-based material is 15-25 μm; (4) The first silicon-based material satisfies (Dv90-Dv10) / Dv50 as 0.7-1.5; (5) The specific surface area of ​​the first silicon-based material is 0.7-2.0 m². 2 / g; (6) The compacted density of the first silicon-based material at 50,000 N is 1.0-1.7 g / cm³. 3 ; (7) The tap density of the first silicon-based material is 1.0-1.5 g / cm³. 3 ; (8) The powder resistivity of the first silicon-based material at 4 MPa is ≤15 Ω•cm; (9) The mass percentage of the first silicon-based material in the first active material is ≤50%; (10) The first silicon-based material includes one or more of elemental silicon, silicon oxide, silicon carbon material, and silicon alloy material.

14. The secondary battery according to claim 13, wherein, The first silicon-based material satisfies at least one of the following (1)-(10): (1) The porosity of the first silicon-based material of the secondary particles is 5%-20%; (2) The volume distribution particle size Dv50 of the first silicon-based material is 10-13 μm; (3) The volume distribution particle size Dv90 of the first silicon-based material is 16-24 μm; (4) The first silicon-based material satisfies (Dv90-Dv10) / Dv50 as 0.9-1.3; (5) The specific surface area of ​​the first silicon-based material is 0.8-1.6 m². 2 / g; (6) The compacted density of the first silicon-based material at 50,000 N is 1.2-1.6 g / cm³. 3 ; (7) The tap density of the first silicon-based material is 1.1-1.4 g / cm³. 3 ; (8) The powder resistivity of the first silicon-based material at 4 MPa is 0.5-12 Ω•cm; (9) The mass percentage of the first silicon-based material in the first active material is 2%-40%; (10) The first silicon-based material includes secondary particles aggregated from at least one of the following primary particles: primary particles of silicon-oxygen material that do not contain alkali metals and alkaline earth metals, primary particles of silicon-oxygen material that contain alkali metals or alkaline earth metals, primary particles of silicon-carbon material, primary particles of elemental silicon, and primary particles of silicon alloy.

15. The secondary battery according to claim 1, wherein, The proportion of the second silicon-based material in the primary particles is 65%-95%.

16. The secondary battery according to claim 1, wherein, The mass percentage of the second silicon-based material in the second active material is less than the mass percentage of the first silicon-based material in the first active material.

17. The secondary battery according to claim 1, wherein, The first silicon-based material and the second silicon-based material satisfy at least one of the following (1)-(5): (1) The volume distribution particle size Dv50 of the second silicon-based material is smaller than that of the first silicon-based material; (2) The specific surface area of ​​the second silicon-based material is smaller than that of the first silicon-based material; (3) The compacted powder density of the second silicon-based material at 50,000 N is greater than that of the first silicon-based material at 50,000 N; (4) The tap density of the second silicon-based material is greater than that of the first silicon-based material; (5) The powder resistivity of the second silicon-based material at 4 MPa is less than that of the first silicon-based material at 4 MPa.

18. The secondary battery according to claim 1, wherein, The second silicon-based material satisfies at least one of the following (1)-(9): (1) The volume distribution particle size Dv50 of the second silicon-based material is 4-12 μm; (2) The volume distribution particle size Dv90 of the second silicon-based material is 8-18 μm; (3) The second silicon-based material satisfies (Dv90-Dv10) / Dv50 as 0.7-1.3; (4) The specific surface area of ​​the second silicon-based material is 0.6-1.6 m². 2 / g; (5) The compacted density of the second silicon-based material at 50,000 N is 1.2-1.8 g / cm³. 3 ; (6) The tap density of the second silicon-based material is 1.1-1.7 g / cm³. 3 ; (7) The powder resistivity of the second silicon-based material at 4 MPa is ≤5 Ω•cm; (8) The mass percentage of the second silicon-based material in the second active material is ≤30%; (9) The second silicon-based material includes one or more of elemental silicon, silicon oxide, silicon carbon material, and silicon alloy material.

19. The secondary battery according to claim 18, wherein, The second silicon-based material satisfies at least one of the following (1)-(8): (1) The volume distribution particle size Dv50 of the second silicon-based material is 5-11 μm; (2) The volume distribution particle size Dv90 of the second silicon-based material is 9-17 μm; (3) The second silicon-based material satisfies (Dv90-Dv10) / Dv50 as 0.8-1.2; (4) The specific surface area of ​​the second silicon-based material is 0.7-1.5 m². 2 / g; (5) The compacted density of the second silicon-based material at 50,000 N is 1.3-1.7 g / cm³. 3 ; (6) The tap density of the second silicon-based material is 1.2-1.6 g / cm³. 3 ; (7) The powder resistivity of the second silicon-based material at 4 MPa is 0.3-4 Ω•cm; (8) The mass percentage of the second silicon-based material in the second active material is ≤15%.

20. The secondary battery according to claim 1, wherein, The negative electrode film layer satisfies at least one of the following (1)-(3): (1) The porosity of the negative electrode film is ≥18%; (2) The compaction density of the negative electrode film is ≥1.5 g / cm³. 3 ; (3) The areal density of the negative electrode film is ≥7 mg / cm³. 2 .

21. The secondary battery according to claim 20, wherein, The negative electrode film layer satisfies at least one of the following (1)-(3): (1) The porosity of the negative electrode film is 25%-45%; (2) The compaction density of the negative electrode film is 1.6-1.8 g / cm³. 3 ; (3) The areal density of the negative electrode film is 12-30 mg / cm³. 2 .

22. An electrical device comprising a secondary battery according to any one of claims 1-21.

Citation Information

Patent Citations

  • Cathode active material, method for preparing same, cathode comprising same, and lithium secondary battery comprising same

    CN108352519A

  • Secondary battery and method for preparing same, and device including secondary battery

    CN113875047A